Strong and tough structural wood material, and methods for fabricating and using the same
By chemically removing lignons from natural wood and compacting in cross directions, the problem of limited improvement in wood mechanical properties in the prior art is solved, and the wood strength and endurance are significantly improved, and it is suitable for a variety of structural applications.
Patent Information
- Application Number
- JP2025015207
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-02-07
- Filing Date
- 2025-01-31
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2038-04-09
AI Technical Summary
The prior art is difficult to effectively improve the strength and endurance of natural wood. The lignon is not removed during the traditional compaction process, which makes it difficult for the wood to completely remove lumen and gaps after compaction, limiting the improvement of its mechanical properties.
The lignon in the wood is partially removed by chemical treatment and the wood is compacted in the cross direction after the lignon is removed, resulting in the lumen of the wood completely or partially collapse, thus forming a tightly intertwined cell wall, enhancing the mechanical properties of the wood.
This method significantly improves the strength and endurance of the wood, enhances its mechanical properties, making it suitable for a variety of structural applications, while reducing the density and thickness of the wood and increasing its application flexibility.
Smart Images

Figure 2025072453000001_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application is a continuation of U.S. Provisional Patent Application No. 62 / 483,828, filed April 10, 2017. and the benefit of U.S. Provisional Patent Application No. 62 / 627600, filed February 7, 2018. No. 6,399,433, filed on Dec. 13, 2003, and which is hereby incorporated by reference in its entirety. [Technical field]
[0002] The present disclosure relates generally to natural wood structures, and more specifically to methods for improving strength and toughness. Chemical treatment and pressing of natural wood for the purpose of building strong and durable wood products The present invention relates to embedded structures and devices. Summary of the Invention [Means for solving the problem]
[0003] An embodiment of the disclosed subject matter provides a method for partially removing lignin from cellulosic natural wood. The chemical treatment provides a strong and durable wood structure. The cellulose nanofibers in the cell walls are aligned to preserve the natural wood lumen. The treated wood is then cooled to room temperature so that the lumens collapse and the residual fluids within the wood are removed. The force component is perpendicular to the direction in which the lumen extends. As a result, the cell walls become entangled and hydrogen bonds form between adjacent cellulose nanofibers. This increases the strength and toughness of the wood, among other mechanical properties. Chemically treated wood can be further modified, manipulated, or machined to provide a variety of structural applications. can be adapted to
[0004] In one or more embodiments, the structure does not substantially maintain the structure of the cellulosic lumen. The lignin is partially removed from the fibrous material by chemical treatment, and the lumen is at least partially A first natural fiber is further pressed in a first direction transverse to the extension direction of the lumen so as to collapse. Includes wood chips.
[0005] In one or more embodiments, the method includes: Natural wood pieces are immersed in a chemical solution to partially remove the lignin while substantially maintaining the structure. This method includes treating the tissue with a septum containing at least one ... The chemically treated wood strip is rotated in a second direction transverse to the first direction for a first time period. A pressing step may also be included.
[0006] In one or more embodiments, the structure has gaps between the cell walls of the lumen in cross section. The compressed wood pieces include pieces in which the lumen has completely collapsed without any cracking.
[0007] In one or more embodiments, the laminate comprises a plurality of compressed wood pieces. Each piece has a cross-sectional In the figure, the lumen can have at least a partially collapsed lumen. The extension directions of at least some of the compressed wood pieces are mutually intersecting. Multiple compressed wood pieces within a laminate can be bonded together.
[0008] Objects and advantages of embodiments of the disclosed subject matter will become apparent from the following description taken in conjunction with the accompanying drawings. It will become clear.
[0009] BRIEF DESCRIPTION OF THE DRAWINGS Embodiments will now be described with reference to the accompanying drawings, which are not necessarily drawn to scale, in which: When applicable, some elements are provided to help illustrate and explain the underlying functionality. For purposes of illustration only, certain elements may be simplified or otherwise not shown. Reference numbers refer to like elements. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 illustrates an exemplary process flow diagram for manufacturing a strong and durable wood-based structure in accordance with one or more embodiments of the disclosed subject matter. [Figure 2A] FIG. 1 is a simplified schematic diagram of a natural wood piece that has been chemically treated to partially remove lignin, in accordance with one or more embodiments of the disclosed subject matter. [Figure 2B] FIG. 2B is a simplified schematic diagram of the chemically treated wood of FIG. 2A after pressing, in accordance with one or more embodiments of the disclosed subject matter. [Diagram 3] FIG. 3A is a simplified diagram of a piece of natural wood that has not been lignin-removed. FIG. 3B is a simplified diagram of the natural wood of FIG. 3A after pressing. FIG. 3C is a scanning electron microscope (SEM) image of a cross section perpendicular to the tree growth direction of the natural wood that has not been lignin-removed. FIG. 3D is an SEM image of a longitudinal cross section parallel to the tree growth direction of the natural wood that has not been lignin-removed. FIG. 3E is an SEM image of a cross section perpendicular to the tree growth direction of the natural wood after pressing. FIG. 3F is an SEM image of a longitudinal cross section parallel to the tree growth direction of the natural wood after pressing. [Figure 4]FIG. 4A is a simplified diagram of a natural wood piece that has been chemically treated to partially remove lignin, according to one or more embodiments of the disclosed subject matter. FIG. 4B is a simplified diagram of the chemically treated wood of FIG. 4A after pressing, according to one or more embodiments of the disclosed subject matter. FIG. 4C is an SEM image of a cross section perpendicular to the tree growth direction of the chemically treated wood after pressing, according to one or more embodiments of the disclosed subject matter. FIG. 4D is an SEM image of a longitudinal cross section parallel to the tree growth direction of the chemically treated wood after pressing, according to one or more embodiments of the disclosed subject matter. FIG. 4E is an enlarged SEM image of region 410 of FIG. 4D, according to one or more embodiments of the disclosed subject matter. FIG. 4F is a schematic diagram showing hydrogen bonds between cellulose nanofibers in the intertwined cell walls of the chemically treated wood after pressing, according to one or more embodiments of the disclosed subject matter. [Diagram 5] Figure 5A is a graph of density values obtained for pressed, chemically treated wood as a function of lignin content, according to one or more embodiments of the disclosed subject matter. Figure 5B is a graph of stress-strain curves of pressed, chemically treated wood for different lignin contents, according to one or more embodiments of the disclosed subject matter. Figure 5C is an SEM image of a longitudinal cross section, parallel to the tree growth direction, of pressed wood after chemical treatment to remove all lignin. [Figure 6] Figure 6A is a simplified diagram of a coated piece of pressed, chemically treated wood in accordance with one or more embodiments of the disclosed subject matter, and Figure 6B is a graph of maximum use temperature versus tensile strength for various construction materials. [Figure 7] FIG 7A is a simplified diagram of wood having its surface chemically treated with a plurality of nanoparticles in accordance with one or more embodiments of the disclosed subject matter. FIG 7B is a simplified diagram of the wood of FIG 7C after pressing in accordance with one or more embodiments of the disclosed subject matter. FIG 7C is an SEM image of the inner surface of the lumen of the wood chemically treated with nanoparticles before pressing in accordance with one or more embodiments of the disclosed subject matter. FIG 7D is a magnified SEM image of region 720 of FIG 7C in accordance with one or more embodiments of the disclosed subject matter. [Figure 8] FIG. 8A is a simplified schematic diagram of an exemplary process for forming strong and durable wood, according to one or more embodiments of the disclosed subject matter. FIG. 8B is a simplified schematic diagram of an exemplary process for forming strong and durable wood using rotary cutting, according to one or more embodiments of the disclosed subject matter. FIG. 8C is a simplified schematic diagram of an exemplary process for forming strong and durable wood from a hollow cylinder of natural wood, according to one or more embodiments of the disclosed subject matter. FIG. 8D is a simplified schematic diagram of an exemplary process for forming strong and durable wood from a solid cylinder of natural wood, according to one or more embodiments of the disclosed subject matter. FIG. 8E is a simplified schematic diagram of another exemplary process for forming strong and durable wood from a solid cylinder of natural wood, according to one or more embodiments of the disclosed subject matter. [Figure 9] FIG. 9A is a simplified schematic diagram of a mechanism for curving pressed, chemically treated wood, according to one or more embodiments of the disclosed subject matter. FIG. 9B is an image of an exemplary curved piece of pressed, chemically treated wood, according to one or more embodiments of the disclosed subject matter. FIG. 9C is a simplified schematic diagram of another exemplary curved piece of pressed, chemically treated wood, according to one or more embodiments of the disclosed subject matter. FIG. 9D is a simplified schematic diagram of a mechanism for machining pressed, chemically treated wood, according to one or more embodiments of the disclosed subject matter. FIG. 9E is an image of an exemplary machined piece of pressed, chemically treated wood, according to one or more embodiments of the disclosed subject matter. [Figure 10A] FIG. 1 illustrates an exemplary process flow diagram for manufacturing a laminated structure from strong and durable wood in accordance with one or more embodiments of the disclosed subject matter. [Figure 10B] FIG. 1 illustrates another exemplary process flow diagram for manufacturing a laminated structure from strong and durable wood in accordance with one or more embodiments of the disclosed subject matter. [Figure 11]FIG. 11A is a simplified diagram of an arrangement of chemically treated wood pieces to form a laminate structure, according to one or more embodiments of the disclosed subject matter. FIG. 11B is a simplified diagram of a laminate structure formed by the wood pieces of FIG. 11A, according to one or more embodiments of the disclosed subject matter. FIG. 11C is a simplified diagram of a multi-layer laminate structure formed with the chemically treated wood pieces of FIG. 11B, according to one or more embodiments of the disclosed subject matter. FIG. 11D is a simplified diagram of another arrangement of chemically treated wood pieces to form a laminate structure, according to one or more embodiments of the disclosed subject matter. FIG. 11E is a simplified diagram of a laminate structure formed by the wood pieces of FIG. 11D, according to one or more embodiments of the disclosed subject matter. FIG. 11F is a simplified diagram of a multi-layer laminate structure formed from the chemically treated wood pieces of FIG. 11E, according to one or more embodiments of the disclosed subject matter. [Figure 12] 12A and 12B are simplified schematic diagrams of an exemplary process for producing strong, durable wood laminates from wood chips and wood sheets, according to one or more embodiments of the disclosed subject matter; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Natural wood is composed of lignin (20% to 35% by weight) and hemicellulose (20% to 3 0% by weight) is a composite of cellulose nanofibers embedded in a matrix. Cellulose, the main component of wood (40% to 50% by weight), is a material that can withstand most metals and It has a higher specific modulus and strength than composites and many ceramics. Also, as shown in FIG. 3A, the lumen 302 (e.g., A unique 3D structure with multiple channels, including tubular channels with cross-sectional dimensions of 20–80 μm. The natural wood 300 has an original porous structure 300. The cell wall 304 of the natural wood 300 is mainly composed of cellulose, heptane, and cellulose. It is composed of cellulose, cellulose, and lignin, as shown in the SEM images of Figures 3C and 3D. These three components intertwine with each other to form a strong, rigid wall structure.
[0012] In an embodiment of the disclosed subject matter, natural wood is subjected to a chemical treatment. The lignin and hemicellulose contents in the wood are significantly reduced, but the cellulose content is The amount of lignin / hemicellulose in the cell wall 304 is only slightly decreased. By removing the oxidizing agent, the wood becomes more porous and less rigid. After chemical treatment, the wood: The direction in which the cellulosic structure extends (i.e., the direction in which the tree grows and the lumen of natural wood extends) Pressed and chemically treated wood (i.e. compressed wood) The wood has at least some strength and toughness improvements compared to natural wood before treatment and pressing. In addition, the mixture may be pressed either before or after pressing to form a hybrid structure. Alternatively, additional materials can be added to the wood. The added materials can be chemically treated and While enjoying the increased mechanical performance offered by compressed wood after pressing, e.g. or by providing fire resistance, adding functionality not available in natural wood. can.
[0013] As used herein, compressed wood refers to wood that has been subjected to the chemical and press treatments described herein. This refers to natural wood (or other natural fiber plants such as bamboo) that has been treated with a chemical process. Lignin and hemicellulose are partially removed, and chemical processing is also performed by this pressing process. By at least partially collapsing (preferably completely collapsing) the inner cavity of the wood that has been subjected to The terms piece and structure are used herein to improve the mechanical properties of wood. Used interchangeably, specific sheets, sticks, strips, bars, blocks, and films It refers to a material that is molded, spun or spun into a molded object, film, or any other shape. In fact, in some cases, it may be pressed and chemically treated. Treated, collapsed wood structures are also called compressed wood or strong wood. In some embodiments, the compressed wood film is thin, i.e., has a thickness perpendicular to the thickness direction. The thickness is smaller than the dimension, for example, the thickness after pressing is less than 200 μm. It is conceivable.
[0014] Referring first to FIG. 1, a generalized process for forming and using compressed wood is shown. 100 is shown. The process 100 can begin at 102, where, for example, For example, you can create a ceiling by cutting it from an existing tree (or other plant) or a block of natural wood. For example, FIG. 3A shows a rectangular cut piece of natural wood 300. However, other starting shapes are possible, such as, but not limited to, a cylindrical or hollow cylindrical shape. 00 has a unique three-dimensional structure with a lumen 302 extending along the direction of tree growth 306. The lumen 302 is bounded by a cell wall 304, which is primarily composed of cellulose. 3C and 3E are scanning electron micrographs showing the morphology and microstructure of natural wood 300. (SEM) images.
[0015] Natural woods include basswood, oak, poplar, ash, alder, aspen, and balsam. Sawood, beech, birch, cherry, butternut, chestnut, cocobolo, elm, hickory, Oak, Padauk, Plum, Walnut, Willow, Yellow Poplar, Bald Eagle Japanese cedar, cypress, Douglas fir, fir, hemlock, larch, pine, sequoia, spruce, and ash Any type of hard or soft wood may be used, including wrack, juniper, and yew. In some embodiments, the natural wood can be any wood other than bamboo. The plant may be any natural fibrous plant.
[0016] After cleavage 102, the process 100 proceeds to 104, where the lignin is partially (but not entirely) separated. Treating the natural wood pieces 300 with a chemical solution to remove the oxidized layer (but not completely) The treatment 104 allows the chemical solution to completely penetrate the cell walls and cavities of the natural wood. To accelerate the process, a vacuum may be used. 1% to 99% (by weight) of the original natural wood lignin is retained, while at least some of it is still present. For example, after chemical treatment, 5% of the lignin in natural wood is removed. % to 95% are removed from natural wood, while at least 20%, at least 40%, At least 60%, or at least 90% (by weight) of the cellulose is retained. In some embodiments, the lignin in natural wood is 23% to 60%. After chemical treatment, 55% of the lignin in natural wood is retained (i.e., 45% is removed). can.
[0017] The chemical solution may include chemicals used in pulping or pulp bleaching, such as Na OH, NaOH / Na2S, NaHSO3+SO2+H2O, NaHSO3, NaHSO 3+Na2SO3, NaOH+Na2SO3, Na2SO3, NaOH+AQ, NaOH / Na2S+AQ, NaHSO3+SO2+H2O+AQ, NaOH+Na2SO3+A Q, NaHSO3+AQ, NaHSO3+Na2SO3+AQ, Na2SO3+AQ, N aOH+Na2S+Na2Sn, Na2SO3+NaOH+CH3OH+AQ, CH3O H, C2H5OH, C2H5OH+NaOH, C4H9OH, HCOOH, CH3COO H, CH3OH+HCOOH, C4H8O2, NH3.H2O, p-TsOH, H2O2 , NaClO, NaClO2 + acetic acid, ClO2, and Cl2 (integer n and AQ are The compound may include at least one of the following:
[0018] In step 106, it is determined whether sufficient lignin has been removed from the natural wood. As with all compressed wood products, 1% to 99% of the lignin is removed, but the final amount varies depending on the application. The amount of lignin removed depends on the soaking time, but the amount of lignin removed depends on the desired mechanical properties of the material. The soaking time may range from as little as 0.1 hours to 72 hours or more, for example, from 0.5 hours to 1 hour. Depending on the desired amount of lignin removal, in addition to or instead of adjusting the soaking time Alternatively, the temperature of the chemical solution may also be adjusted. may be boiled, which may affect a larger amount of lignin compared to a non-boiled solution. In some embodiments, the chemical solution may have an alkaline pH value. The liquid was a boiling solution of 2.5M NaOH and 0.4M Na2SO3, and the immersion time was It can be 0.5 to 7 hours.
[0019] Once sufficient lignin has been removed by the treatment at 104, the process 100 continues to The wood pieces may then be optionally rinsed. Rinsing may include, but is not limited to, washing with deionized water ( The method may include soaking the treated wood pieces in a solvent such as DI water. In this embodiment, the solvent may be at a high temperature, such as boiling. and / or are effective in removing remnants of chemical solutions within wood components removed by treatment. In some embodiments, it may be desirable to retain the removed components of the wood. In that case, rinsing may be omitted.
[0020] After rinsing (or after completion of step 104 if there is no rinsing), process 100 optionally The process can proceed to 108, where the chemically treated wood is subjected to pre-press corrections. For example, the optional modification 108 may result in the formation or deposition of non-natural particles on the surface of the chemically treated wood. Such a surface may include an inner surface, for example, the inside of a lumen. The surface of the chemically treated wood may include the cell walls and the outer surface of the chemically treated wood. Non-natural particles incorporated into the cellulose provide, among other functions, hydrophobicity, weather resistance, and corrosion resistance (e.g. To provide the final compressed lumber with certain advantageous properties, such as resistance to salt water, and / or fire retardancy. For example, in one embodiment, hydrophobic nanoparticles (e.g., SiO nanoparticles) on the surface of chemically treated wood, as further described below with respect to Figures 7A-7E. It can be formed into.
[0021] Alternatively or additionally, the optional modification 108 may involve adding a polymer to the chemically treated wood. or further chemical treatment to modify the surface of the chemically treated wood to obtain advantageous properties. For example, the modification step of 108 for providing hydrophobicity may be included. Chemical treatments include epoxy resins, silicone oils, polyurethanes, and paraffin emulsions. John, Acetic anhydride, Octadecyltrichlorosilane (OTS), 1H,1H,2H,2H -Perfluorodecyltriethoxysilane, Fluoroecin, Polydimethylsiloxane ( PDMS), methacryloxymethyltrimethylsilane (MSi), polyhedral oligomers POSS, potassium methylsiliconate (PMS), dodecyl (trimethylsilyl) Trimethoxysilane (DTMS), Hexamethyldisiloxane, Dimethyldiethoxysilane silane, tetraethoxysilane, methyltrichlorosilane, ethyltrimethoxysilane, Triethoxysilane, trimethylchlorosilane, phenyltrimethoxysilane, phenyl Propyltriethoxysilane, Propyltrimethoxysilane, Polymethylmethacrylate, Poly Diallyldimethylammonium chloride (polyDADMAC), 3-(trimethoxysilyl) Silyl)propyl methacrylate (MPS), hydrophobic stearic acid, amphiphilic fluorinated tri Block azide copolymer, polyvinylidene fluoride and fluorinated silane, n-dodecyl trimethoxysilane, and sodium lauryl sulfate.
[0022] For example, further chemical treatments of 108 to provide weathering or corrosion resistance include CDDC (cupramate), ammoniacal copper quaternary (ACQ), chromated copper arsenate (CCA), ammoniacal copper arsenate Acid Copper Zinc Arsenate (ACZA), Copper Naphthenate, Acid Copper Chromate, Copper Citrate, Copper Azole , 8-hydroxyquinoline copper, pentachlorophenol, zinc naphthenate, copper naphthenate , creosote, titanium dioxide, propiconazole, tebuconazole, cyproconazole , boric acid, borax, organic iodide (IPBC), and Na2BO 13 4H2O capsule At least one of these is included.
[0023] After any modification 108, the process 100 can proceed to 110, where a chemical treatment The wood is pressed in a direction transverse to the direction of extension of the bore. For example, the press 110 is The press 110 is applied in a direction substantially perpendicular to the direction of extension of the bore, or the press 110 is applied in a direction substantially perpendicular to the direction of extension of the bore. The press 110 can reduce the thickness of the wood, This increases the density of the wood and eliminates voids or gaps within the cross section of the wood. For example, the press 110 may be operated at a pressure of 0.5 MPa to 10 MPa, for example. In some embodiments, pressing can be performed at room temperature. While the pressing may be performed at elevated temperatures (i.e., cold pressing), in other embodiments, pressing is performed at elevated temperatures. For example, the pressing may be performed at a temperature of 20° C. to 120° C., for example at 1 It may be carried out at 00°C.
[0024] The press 110 may include an intermediate drying stage after processing 104 and / or any modification 108. As a result, chemically treated wood retains water in it. Therefore, the press 110 removes the water retained in the chemically treated wood. It is possible to remove the residuals and reduce the thickness of the wood to increase its density. During the experiment, hydrogen bonds formed between the remaining cellulosic nanofibers in the wood cell walls. The mechanical properties of the wood are improved. Or particles or material formed within the wood can be retained after pressing and on the inner surface The particles / material become embedded in the collapsed lumen and within the intertwined cell walls.
[0025] The press 110 is used to remove water and allow desirable hydrogen bonds to form. For example, chemically treated wood can be subjected to a variety of temperature, relative humidity and Hold under pressure for at least 5 minutes, although other times are possible depending on factors such as the material and type of wood. For example, chemically treated wood can be stored for at least 1 hour. Can be held under pressure for 2 hours, at least 24 hours, or at least 48 hours. do.
[0026] FIG. 2A shows a bore 202 extending along a direction 206 and a cavity 204 aligned along the direction 206. and a wall 204 made of cellulose-based nanofibers. The block 200 is subjected to a press 208 in a direction intersecting with the extension direction 206. This results in the compressed wood structure 210 of FIG. As a result, the lumen 202 can be completely collapsed, as shown at 212, and the cell wall 204 can be intertwined. The pressing is performed so that the thickness W2 of the block 210 after pressing is It can be reduced by at least 10% compared to W1 of block 200. For example, thickness W2 may be 60%, 70%, or 80% thicker than W1 of block 200. For example, the compression ratio (W1:W2) of a press can be reduced by 1.1:1 to 10:1. It is possible.
[0027] After pressing 110, the process can optionally proceed to 112, where the compressed wood is For example, optional modification 112 may be applied to the exterior surface of the pressed wood (e.g. The method may include forming or depositing a coating (on the non-natural particle). The coatings are designed to provide, among other properties, hydrophobicity, weather resistance, corrosion resistance (e.g., salt water resistance), and / or certain advantageous properties, such as fire retardancy, may be included in the compressed wood. For example: The coating can be oil-based paint, hydrophobic paint, polymer coating, or fire-resistant coating. This may include
[0028] In one embodiment, the fire-resistant coating of nanoparticles (e.g., BN nanoparticles) is As will be further described below with respect to Figures 6A-6B, a compressed wood material may be formed on the outer surface of the compressed wood material. Alternatively or additionally, the coating of modification 112 may be boron nitride, montmorillonite, or the like. Clay, hydrotalcite, silicon dioxide (SiO2), sodium silicate, calcium carbonate Calcium (CaCO3), Aluminum Hydroxide (Al(OH)3), Magnesium Hydroxide , (Mg(OH)2), magnesium carbonate (MgCO3), aluminum sulfate, iron sulfate, Zinc borate, boric acid, borax, triphenyl phosphate (TPP), melamine, polyurethane , ammonium polyphosphate, phosphoric acid, phosphate ester, ammonium phosphate, ammonium sulfate ammonium, phosphonic acid, diammonium phosphate (DAP), ammonium dihydrogen phosphate, Monoammonium phosphate (MAP), guanylurea phosphate (GUP), guanidinium dihydrogen phosphate The material may include at least one of antimony pentoxide, antimony pentoxide, and antimony pentoxide.
[0029] After any modification 112, the process 100 may optionally proceed to 114, where: For example, by machining or manipulating compressed wood to change its structure or shape The compressed wood can then be prepared for its final use. Machining processes include cutting (e.g., Machining, drilling, lathing, tapping, boring, carving, routing, sanding These processes may include, but are not limited to, milling, grinding, and abrasive tumbling. Processes include, but are not limited to, bending, forming, and other forming techniques. .
[0030] After any machining or manipulation 114, the process 100 can proceed to 116, Compressed wood can therefore be used in certain applications because of its improved mechanical properties. Compressed wood can be used in a variety of structures and applications. For example, compressed wood can be used in the following ways: It is adaptable. Exterior components (e.g. body panels, door panels, roofs, bumpers, front rings, roofs, trim, masts, etc.), internal structural components (e.g. chassis, frame rails, cross beams, fuselage frames, wing frames, etc.) or automobiles, Trucks, motorcycles, trains, aircraft, ships, spacecraft, watercraft or other vehicles, cars or vehicle interior components (e.g. door panels, liners, handles, handrails, flooring, seats, trim, storage bins or shelves, etc.); Exterior components (e.g., exterior walls, siding, roofs, shutters, etc.), interior structural components Components (e.g., frames, studs, wall panels, lintels, cross beams, load-bearing beams, subfloors, etc.) or the interior components of a home, office, barn, warehouse, tower, or other building or structure Components (doors, door frames, window frames, picture frames, walls, flooring, panels, ceilings, trim , stairs, handrails, etc.); Decks, awnings, docks, patios, bridges, poles, bleachers, or Platform structural components; Furniture (e.g. chairs, benches, desks, tables, cabinets, wardrobes, counters, tops, etc.) or their internal structural components (e.g. sofa or chair frames furniture, bed frames, etc.), or home accents or décor; Musical instruments (e.g. piano, guitar, violin, harp, zither, drums, etc.), sports Sports equipment (e.g. golf clubs, ping pong tables and paddles, basketball backboards) a goal, goal post, baseball bat, etc.), a tool (e.g., a hammer hand tools, broom handles, saws, etc.); or Protective components (e.g. computer cases, mobile phone cases, blast shields) enclosures, containers, boxes, shipping crates, packaging, or is housing.
[0031] The above list of uses of compressed wood is not exhaustive. Depending on the aspect, applications of compressed wood beyond those specifically listed are possible. Based on the teachings provided herein, one of ordinary skill in the art will readily appreciate that compressed wood can be adapted for other uses. will understand.
[0032] In a conventional compression process, natural wood 300 is pressed without removing the lignin. Often, wood is pretreated (e.g., exposed to steam, heat, or ammonia, or cold These pretreatments can soften the wood structure, but they also have the potential to damage the wood. The resulting pressed wood is shown in Figure 3B. The wood 308 has a reduced thickness (i.e., along direction 312) compared to the original natural wood. For example, conventional compression processes are limited to approximately 60% reduction in thickness. If the lignin is not removed, the natural wood 300 is pressed to completely remove the inner cavity 302. It is difficult to break down the wood into smaller pieces and eliminate other voids from the cross section. Partial recovery of the thickness of 0.8 can occur after pressing. Therefore, conventional methods that do not remove lignin The compressed wood 308 is composed of collapsed fine grains, as shown in the SEM images of FIG. 3B and FIG. 3E-FIG. 3F. It suffers from numerous gaps 310 between the cell walls 304.
[0033] In contrast, according to embodiments of the disclosed subject matter, partially deligninized compressed wood The process completely collapses the cavity of natural wood, eliminating the spaces between the cell walls and allowing the cell walls to form tightly packed together. This results in a unique intertwined layer structure, which provides excellent mechanical properties. For example, wood 200 that has been chemically treated to partially remove lignin can be pretreated. As shown in FIG. 4B, the wood cavity 202 and the porous cell walls 204 are The partial removal of lignin causes the press to produce a significant reduction in thickness, e.g. , reduce the thickness by at least 5:2 (e.g., 70% to 80% reduction) and increase the density. The concentration of 100 mM NaCl can be increased (e.g., by about 3-fold).
[0034] As shown in the SEM images of FIGS. 4C-4D, the previously hollow lumen 202 is now completely The wood cell wall 204 is broken down into small pieces, forming a highly intertwined wood cell wall. Even holes are eliminated by compression. Compressed wood 210 is tightly intertwined along its cross section, Completely collapsed wood cells that are tightly packed along their length (i.e., direction 206). Furthermore, as shown in FIG. 4E, the cell wall 204 is The nanofibers 214 are similar to those in natural wood, but much more densely packed (e.g. 206).
[0035] By chemical treatment and subsequent pressing, adjacent cellulose nanofibers were separated, as shown in Figure 4. Hydrogen bonds 216 are formed between the fibers 214. These hydrogen bonds 216 are In particular, the densely packed compressed wood 210 can contribute to improving the mechanical properties of the compressed wood. The intertwined microscale wood cell walls204 are composed of cellulose nanofibers214 This results in a high degree of alignment and therefore a dramatic increase in the interfacial area between the nanofibers 214.
[0036] The abundance of hydroxyl groups in the cellulose molecular chains allows the densely packed wood cell walls to be The relative sliding between the 4 molecules causes numerous hydrogen bond formation-breaking-reformation events on a molecular scale. As a result, the total energy required to break compressed wood is 10 times that required to break natural wood. In other words, compressed wood is much stronger than natural wood. In addition, the dense microstructure significantly reduces both the amount and size of defects in compressed wood. Therefore, it has much higher strength than natural wood. Exemplary values for the mechanical properties of a wood material (e.g., basswood with 45% lignin removal) are shown in Table 1 below. vinegar.
[0037] The mechanical properties of compressed wood are not only superior to those of natural wood, but also have many widely used The properties of the construction materials used (e.g., plastics, steel, and alloys) are better understood. In fact, the demonstrated tensile strength of compressed wood is greater than that of conventional compressed wood that does not remove lignin. Like wood, ordinary plastics (e.g., nylon 6, polycarbonate, polystyrene) The tensile strength of compressed wood is much higher than that of compressed ethylene and epoxy. The significant increase in tensile strength is not affected by the decrease in toughness. The inherent lightness of cellulose is at least 300MPa cm 3 / g, for example, about 450 MPa cm 3 / g compression The specific strength of wood is calculated by multiplying the specific strength of titanium alloy (e.g., about 244 MPa) cm 3 / g).
[0038] [Table 1]
[0039] Table 2 shows the results for natural wood, delignified wood without hot pressing (sample 1), and delignified wood without hot pressing. Compressed natural wood (sample 2), and compressed wood (pressed after delignification - sample 3) The axial compressive strength (along the direction of the lumen) of the rig is compared. At least partial removal of the nin completely collapses the lumen and causes the cell walls to intertwine. This is necessary so that the resulting compressed wood can achieve excellent strength and toughness. do.
[0040] [Table 2]
[0041] However, the mechanical properties of the resulting compressed wood are not as distinct from those of the natural wood before pressing. As reflected in the data in Table 3, The amount of lignin removed can be a function of time in the chemical solution. Stress-strain of de-nified compressed wood samples and un-pressed natural wood samples Table 3 shows the curves for compressed wood samples with various levels of deligninization and pressed wood samples. The composition and mechanical properties of the untreated and untreated natural wood samples are shown in Table 3. In Figure 5A to Figure 5B, NW refers to natural wood that has not been pressed, and DW-x refers to wood that has had lignin removed. As is readily apparent from the data, 45% lignin Compressed wood with lignin removed (e.g., 11.3% lignin content) is the best for basswood. High strength and toughness, but other removal rates are best suited for other types of wood or different applications. There are cases like this.
[0042] [Table 3]
[0043] The resulting density of the compressed wood also decreased with increasing pressure, as reflected in the graph in Figure 5A. If lignin removal is less than 45%, the resulting The density of compressed wood increases with the degree of lignin removal. This is due to at least three factors: First, as more lignin is removed, more pores appear in the cell walls. Second, the cell walls of chemically treated wood decrease with increasing time in the chemical solution. The increase in time required to produce the desired increase in lignin removal is Third, the structure after chemical treatment retains at least some lignin as a binder. However, if excessive lignin is removed (e.g., As shown in the SEM image in Figure 5C, when approximately 100% of the phosphorus is removed, The wood structure crumbles easily, thus inhibiting the ability to densify the structure by pressing. will be done.
[0044] [Table 4]
[0045] Results for specific wood species are discussed herein and shown in Tables 1-3 and Figures 5A-5B. Although similar results have been obtained for other types of wood or other plants (e.g., bamboo), For example, Table 4 shows the results of the analysis of various types of natural wood and compressed wood (partially depleted of lignin). Exemplary values of mechanical properties are shown for the tensile strength and stiffness (removed before and after the test). Thus, the teachings of the present disclosure are applicable to a wide variety of It is applicable to a wide range of plant species.
[0046] Compressed wood is stable under moisture attack, e.g., at 95% relative humidity (RH). ) for 128 hours, the compressed wood expanded in thickness by approximately 8.4% to 493.1 MPa. There is a slight decrease in tensile strength (e.g., less than 20%) at ambient temperature, which is comparable to that of natural wood in ambient conditions. This is still an order of magnitude greater than the tensile strength of the material.
[0047] Further protection of the properties of compressed wood from environmental factors or the introduction of new properties is possible through post-pressing. Modification 112 can be used to provide a coating that can be applied to compressed wood, for example, oil-based paint, hydrophobic paint, etc. or coated with a polymer coating to provide substantial protection from environmental moisture. In another example, the compressed wood 602 may be formed by cutting its outer surface as shown in FIG. 608. Such a coating 604 may be formed on the substrate 602. 4 allows the composite structure 600 to conduct heat 606 along the surface 608, This minimizes or at least reduces the temperature rise inside the composite structure (i.e., compressed wood 602). Reduce.
[0048] The coating 604 may function as a flame retardant coating. The adhesive coating 604 is a BN nanosheet (e.g., a cellulose acetate nanosheet bonded to the surface of the compressed wood 602). Such a composite structure may be a boron nitride (BN) coating, such as a layer of nanoparticles. The structure 600 may be made of uncoated compressed wood 200 (614 in FIG. 6B) or other suitable Compared to conventional structural materials, it has at least the tensile strength and maximum service temperature (612 in FIG. 6B). The critical temperature of compressed wood is a single point 61°C. 2, but can range from 300°C to 500°C with a tensile strength of 600 MPa. In another embodiment, the flame retardant coating comprises montmorillonite clay. may additionally be provided with, for example, hydrophobic, weather-resistant or corrosion-resistant, resistant to corrosion, as described above with respect to FIG. After treatment, compressed wood can be given different surface treatments to improve its chemical or fire resistance. can.
[0049] Alternatively or additionally, protecting the properties of compressed wood from environmental factors or introducing new properties. This can be provided by pre-press modification 108, e.g., by further chemical processing. By adding functional materials such as nanoparticles or polymers to chemically treated wood, it is possible to improve water resistance. Strength, corrosion resistance, weather resistance, chemical resistance, fire resistance, and / or other properties of the final compressed timber can be included in
[0050] In one embodiment, the inner surface and the inner surface of the chemically treated wood are treated to provide superhydrophobicity to the compressed wood. and nanoparticles can be formed on the outer surface. As used herein, superhydrophobicity refers to Defined as a static water contact angle (CA) greater than 150° and a dynamic roll angle less than 10° Such superhydrophobicity improves the corrosion resistance of construction materials in humid conditions, thereby stabilizing In another embodiment, the nanoparticles improve the compressible wood at least in part. Hydrophobicity may be introduced so that the surface exhibits a static contact angle of 90° or a dynamic contact angle of less than 10°. For example, the nanoparticles can be SiO2 nanoparticles.
[0051] As with the other embodiments above, the chemically treated wood is first decomposed into hemicellulose and lysine. The porous cell wall 704 and lumen 702 are formed by partially removing the lignin. The chemically treated wood 700 is then processed by applying pressure to the inner and outer surfaces of the wood 706, as shown in FIG. and is subjected to further chemical treatment which causes in situ growth of nanoparticles 708 on the outer surface. For example, chemically treated wood 700 contains tetraethyl orthosilicate (TEOS) and and heptadecafluoro-1,1,2,2-tetradecyltrimethoxysilane (17F) (e.g., 3 ml of TEOS, 3 ml of NH3 H2 in 100 ml of ethanol) The immersion can be performed at elevated temperatures (e.g., 50 ℃) for a long time (e.g., 10 h) to obtain modified SiO2 nanoparticles by the sol-gel method. For example, the diameter of the nanoparticles is about 100 nm. As a result of the formation of nanoparticles 708, as shown in the SEM images of Figures 7C-7D. In addition, the particles can be distributed evenly on both the wood surface and inside the cavity 702.
[0052] The treated wood 706 decorated with SiO2 nanoparticles 708 is then heated (e.g., at 100° C. 7B. The pressing removes (or nearly completely removes) the space between the channel walls 704. Thus, there are multiple entangled layers 712 and aligned cellulose nanofibers within each layer. The result is a laminated structure with SiO2 nanoparticles. The molecules are held between the intertwined layers. Thus, together with the in situ growth of SiO2 nanoparticles, Finally, the well-preserved micro / nano hierarchical structure endows compressed wood 710 with superhydrophobicity. For example, the compressed wood 710 may be formed by compressing a water droplet placed on a surface 716 of the wood 710. Drop 714 may exhibit static and dynamic contact angles of 159.4° and 3°, respectively. The nanoparticles 708 can also impart resistance to acidic / alkaline conditions.
[0053] The superhydrophobicity may also provide the compressed wood with anti-swelling properties. In particular, the compressed wood 710 has a 24 hour It absorbs very little water when immersed in water for a long period of time, a very low amount of about 1.8%. This suggests that the compressed wood 710 repels water strongly. In contrast, natural wood exhibits significant expansion when exposed to the same conditions, e.g., 119%. The excellent hydrophobicity of the compressed wood 710 allows it to expand in wet or other unfavorable conditions. Maintains dimensional stability and decay resistance of wood even when exposed to low or harsh outdoor conditions can be significantly improved.
[0054] Additionally, the nanoparticle treatment within the wood microstructure of the compressed wood 710 enhances the wear resistance of the treatment. In the experiment, sandpaper (120 mesh) was applied to the top and bottom surfaces of the wood during compression. The resulting compressed wood 710 has micrometer-sized roughness The initial static and dynamic contact angles of water on compressed wood were 159.2° and 159.7°, respectively. and 3°. 10, 20, 30, and 40 abrasion cycles with sandpaper After that, 158.1° / 4.5°, 156.3° / 5.9°, and 152.9° / 7. The static contact angle was reduced by 100% with each cycle. (and a minimal increase in the dynamic contact angle), the hydrophobic treatment of the compressed wood 710 is It is clear that the layered structure after compression is composed of well-dispersed nano-SiO2 spheres. By trapping the body, the nanoparticles are firmly anchored to the wood, resulting in robust superhydrophobicity. can be done.
[0055] Referring now to FIG. 8A, an exemplary method for forming a compressed wood structure from natural wood 802 is shown. The manufacturing process of natural wood 802 is shown in Fig. 1. The natural wood 802 can be in the form of sheets, sticks, strips, It may be a bar, block, membrane, film, or any other shape of wood. The lumen in 802 may extend along direction 806. 800 includes, for example, a chemical solution 804, as described above with respect to 104 of process 100. A step of soaking natural wood 802 to partially remove lignin from the wood 802. The chemical solution 804 and the wood 802 that is immersed therein are contained within a housing 808. In some embodiments, the housing 808 is a vacuum housing. Alternatively, the solution 804 and wood 802 may be kept under vacuum during soaking. Additionally, the housing 808 or another component therein may be configured to keep the solution 804 at a temperature above room temperature. For example, the solution 804 can be heated to a boil during the chemical process 800. It may be heated at .
[0056] After the process 800, the chemically treated wood 816 may be, for example, As described above, the direction is generally perpendicular to the extending direction 806 or slightly different from the extending direction 806. 8, from the housing 808 to the compression station 810 for pressing in at least one cross direction. For example, the compression station 810 may include an upper platen 814 and a lower platen 815. The platens 814, 818 may include a second platen 818. Relative motion between the platens 814, 818 may The chemically treated wood 816 is subjected to a desired compression to produce compressed wood. The main platen 814 remains stationary to apply a compressive force 812 to the wood 816. The platen 81 may move toward a lower platen 818 that supports the wood 816. Both 818 and 814 may move toward each other to apply a compressive force 812.
[0057] In some embodiments, the temperature of the wood 816 is increased above room temperature during compression. Either or both platens 814, 818 may be heated. The platens 814, 818 may not be heated, but may be heated to raise the temperature of the wood 816. To achieve this, a separate heating mechanism may be provided, or the environment containing the compression station may be heated. This is also fine.
[0058] Referring to FIG. 8B, another exemplary method for forming a compressed wood structure from natural wood 832 is shown. The manufacturing process is shown. The natural wood 832 can be in the form of logs or cylindrical bars. , the bore extends in a direction perpendicular to the page. The reelase 834 is used to cut the natural wood 832 and separate the natural wood for further processing. A thin continuous layer 836 can be separated. The natural wood layer 836 is then Step 830, e.g., by dissolving the chemical solution 80 in a solution as described above with respect to step 104 of process 100. 4, the wood 836 is transported to a housing 838 for a step of soaking the wood 802. The lignin can be partially removed from the housing 808. 38 may be configured to apply vacuum and / or heat during immersion. In some embodiments, the size of the housing 838 and the thickness of the natural wood 832 for the housing The speed of transport of layer 836 through 838 can correspond to the desired immersion time for the chemical treatment. Thus, a portion of layer 836 enters housing 838 and is then compressed at a compression station 840. The time it takes for the lignin to leave the housing 838 is determined based on the soak time for the desired amount of lignin removal. will respond.
[0059] After treatment 830, the substrate may be chemically treated, for example as described above with respect to 110 of process 100. The wood 848 is oriented in a direction substantially perpendicular to the extension direction, or at least in a direction intersecting the extension direction. The molded article can be transported from the housing 838 to a compression station 840 for pressing in the forward direction. For example, compression station 840 includes upper rollers 844 and lower rollers 846. They can be held at a fixed distance from each other. The thickness of the processed wood 848 may be smaller than the thickness of the processed wood 848, thereby resulting in a compressed wood. A force 842 is applied.
[0060] In some embodiments, the temperature of the wood 848 is increased above room temperature during compression. Either or both rollers 844, 846 may be heated. The rollers 844, 846 do not need to be heated, but they are heated to raise the temperature of the wood 848. A separate heating mechanism may be provided, or the environment containing the compression station 840 may be heated. It may be heated.
[0061] Although only two rollers 844, 846 are shown in FIG. 8B, the conveyance of the sheet 848 A plurality of rollers may be arranged in series along the direction. Between adjacent rollers to provide a compression time (e.g., minutes or hours) Alternatively or additionally, rollers 84 may be provided to hold the material under pressure as it is transported. 4, the size of 846 and the speed at which the sheet 848 is conveyed can correspond to the desired compression time. Thus, from the time when the sheet 848 is first compressed, it is compressed into a compressed lumber 850 at the compression station. The time to exit the press 840 will correspond to the desired press time. , the compression station 836 may be cut before or after chemical treatment 838. It is also possible to separate the compression step 840 from the chemical process 838. The station may be in the form of a roller as shown in FIG. 8B or a flat plate as shown in FIG. 8A. It may take the form of a flat platen.
[0062] Referring to FIG. 8C, an exemplary manufacturing method for forming a compressed wood structure from natural wood 862. The process is shown in Fig. 8. Natural wood 862 has an internal cavity extending along direction 864. The first step 860 of the manufacturing process is, for example, As described above with respect to process 100, 104, natural wood 862 is soaked in a chemical solution 804. The chemical solution 804 and the lignin solution 805 can partially remove lignin from the wood 862. The wood 862 immersed therein is vacuumed during immersion, similar to the housing 808 of FIG. 8A. The composition may be configured to apply and / or heat.
[0063] After treatment 860, the chemically treated wood cylinder 868 may be, for example, 110 of process 100. As described above with respect to the extension direction 8 (perpendicular to the plane of the page at 807 in FIG. 8C ), 64 or in a direction at least intersecting the extending direction 864. For example, the compressed air may be transported from the housing 866 to a compression station 870 for compression. The portion 870 includes an upper roller 872 disposed on the outside of the cylinder 868 and a and a lower roller 874 disposed inwardly. , the walls of the cylinder 868 can remain at a constant distance from each other as they pass through them. The distance may be less than the wall thickness of the chemically treated wood 868, thereby A pressing force 876 is applied resulting in a hollow cylinder of
[0064] In some embodiments, the temperature of the wood 868 is increased above room temperature during compression. Either or both rollers 872, 874 may be heated. The rollers 872, 874 may not be heated, but may be heated to raise the temperature of the wood 868. Alternatively, a separate heating mechanism may be provided, or the environment containing the compression station 870 may be heated. This may be done.
[0065] Although only two rollers 872, 874 are shown in FIG. 8C, multiple rollers may be used in a circular The walls of the cylinder 868 may be arranged in series around the circumference of the cylinder 868. (e.g., minutes or hours) between adjacent rollers. Alternatively or additionally, the rollers 872, 874 may be kept under pressure. The size and rotational speed of cylinder 868 may correspond to a desired compression time.
[0066] Referring to FIG. 8D, an exemplary manufacturing method for forming a compressed wood structure from natural wood 882. The process is shown. Natural wood 882 has an internal cavity extending along direction 884. The first step 880 of the manufacturing process may be, for example, a process As described above with respect to 104 of the stone 100, the natural wood 882 is immersed in the chemical solution 804. , which can partially remove lignin from wood 882. The wood 882 that is immersed in the housing 808 of FIG. 8A is provided with a vacuum during immersion. The device may be housed within a housing 866, which may be configured to receive and / or heat the device. stomach.
[0067] After treatment 880, the chemically treated wood cylinder 886 may be, for example, 110 of the process 100. As discussed above with respect to the extension direction 88 (perpendicular to the plane of the page at 890 in FIG. 8 ). 4 or in a direction at least intersecting the extending direction 884. From the jigs 866 to the compression station 890. 90 may include a single roller 888 disposed on the outside of a cylinder 886. The roller is supported and rotatable about its central axis. The compressed wood can be pressed into the wall of the cylinder 886 at a certain distance during compression. A pressing force 892 is applied which results in a solid cylinder.
[0068] In some embodiments, the temperature of the wood 886 is raised above room temperature during compression. Alternatively or additionally, roller 888 can be heated. Although not required, a separate heating mechanism may be provided to increase the temperature of the wood 886. , or the environment containing the compression station 890 may be heated.
[0069] Although only a single roller 888 is shown in FIG. 8D, multiple rollers may be mounted on a cylinder 886. The cylinders 886 may be arranged in series around the minutes or hours) while being conveyed between adjacent rollers under pressure Alternatively or additionally, the size of the roller 888 and the cylinder 8 The rotational speed of 86 may correspond to the desired compression time. , as shown in FIG. 8E, instead of a compression station 890 having rollers 888 , may be pressed by a compression belt 894 at a compression station 895. In some configurations, the cylinder 886 may remain stationary rather than rotating.
[0070] Although specific wood configurations and manufacturing techniques are illustrated in Figures 8A-8E, one or more of the following may be used: Other shapes (solid or hollow) and manufacturing techniques are possible, depending on the embodiment being described. Therefore, the shape and manufacturing technique of the wood are not limited to those specifically shown. The stations, as well as the pre-press and post-press corrections, are not shown in FIGS. 8A-8E. Although not shown, these techniques may be used in accordance with one or more embodiments of the disclosed subject matter. , can be easily modified to include pre-press and / or post-press modifications.
[0071] Once the chemically treated wood pieces have been compressed to form compressed wood, e.g., in process 100, As discussed above with respect to 114, further processing (i.e., machining or For example, compressed wood 902 can be made as shown in FIG. The compressed lumber 902 can be placed in a bending setup 900. For example, a cylindrical rod) is placed on the support 906 while being pressed against its upper surface. By maintaining pressure through bending tool 904 for a period of time, e.g., as shown in FIG. 9C or 912 of FIG. 9C. A profile 908 can be introduced into the compressed timber 902. Alternatively or additionally, The compressed wood can be subjected to conventional machining techniques. For example, FIG. 9D shows a machined 9 shows a setup 920 in which a press 922 with a drill bit 924 is 9E, creating a through hole 928 in the compressed wood piece 926. According to contemplated embodiments, other types of post-press modifications and / or machining may be performed. is also possible.
[0072] In an embodiment of the disclosed subject matter, the cellulose of natural wood is converted into wood fiber by chemical treatment and pressing. This maintains the alignment of the nanofibers, thus resulting in the anisotropic mechanical properties of compressed wood. For example, in a tensile test of compressed wood in the direction perpendicular to the fiber alignment, the tensile strength was 45.1 MPa. This is much lower than the strength along the fiber alignment direction, but it is comparable to that of natural wood. Much higher than the transverse strength (e.g., 5.7 MPa). Reduces anisotropy (also The compressed pieces can be bonded into a laminate structure to improve mechanical properties. .
[0073] Referring to FIG. 10A, a generalized method for forming and using compressed wood laminate structures is shown. A process 1000 is shown. Similar to the process 100 of FIG. , cleavage 102, chemical treatment 104 to remove sufficient lignin 106, and then These initial processes may include pressing 110 of treated wood. This is repeated to produce multiple individual compressed lumber pieces.
[0074] Once a sufficient number of compressed wood pieces are prepared, the process 1000 can proceed to 1004. , where the compressed wood pieces are optionally subjected to a surface treatment. The pieces are bonded together using adhesive or epoxy. Preparation 1004 may include applying an adhesive or epoxy to opposing surfaces of the compressed wood pieces. In other embodiments, the final hydrogen bonds between the opposing faces of the compressed wood pieces can It may be sufficient to hold them together, in which case preparation 1004 may be omitted.
[0075] The process 1000 can proceed to 1006, where the compressed wood pieces are sintered in preparation for joining. Each compressed piece of wood can have a respective orientation, which The alignment 1006 corresponds to the direction in which the lumen extends before pressing. Arranging the compressed wood pieces so that at least some of the pieces have different orientations relative to each other. For example, FIG. 11A shows a compressed wood having a first orientation 1103. and a second piece of compressed wood 110 having a second orientation 1105. 11B shows a set 1100 of laminates having a laminate structure 1100 of 4 and 1100 of 5 pieces. When joined as 1106, the first orientation 1103 is perpendicular to the second orientation 1105. A first piece 1102 and a second piece 1104 can be placed on the
[0076] The tensile strength of the compressed wood laminate in Figure 11B along the two perpendicular wood fiber directions is approximately the same. (e.g., 221.6±20 MPa and 225.6±18 MPa, respectively), Compressed wood (e.g., 43.3±2MPa) or natural wood (e.g., 5.1±0.4MPa a) significantly higher than the strength in the T direction (i.e. perpendicular to the wood grain direction) of a single piece expensive.
[0077] In other embodiments, the orientation of the joined compressed wood pieces is non-perpendicular to each other. For example, FIG. 11D shows another set of laminates 1110, this time with the first compressed wood. The piece 1112 has a first orientation 1113 that is different from that in FIG. 11A. As shown in FIG. 1, when the first piece 1112 is joined to the second piece 1104, the top view of the first piece 1112 is In this case, the direction of the first piece 1113 intersects with the direction of the second piece 1105. To insert.
[0078] As shown in FIG. 11C, multiple sets 1100 are joined together to form each piece of compressed wood. The multi-layer 1106 laminate structure is arranged such that each piece has a 90° rotated orientation relative to the adjacent pieces. Similarly, multiple sets 1110 can be formed together as shown in FIG. Joined together, each piece of compressed wood has a different orientation than the adjacent pieces, and / or or multiple layers 1116, such that each layer has a composite orientation that is different from the composite orientation of the adjacent layers; 1118 A stacked structure can be formed.
[0079] A specific number of compressed wood pieces for a laminated structure are shown in Figures 11A to 11F. Other numbers of compressed wood pieces are possible according to the above contemplated embodiments. Although a rectangular shape is shown in FIG. 11F, according to one or more contemplated embodiments, Additionally, other shapes are possible. Other orientations and alignments are possible according to one or more contemplated embodiments. In an embodiment, the orientation of adjacent pieces of wood may be aligned, for example to enhance anisotropy. can.
[0080] Returning to FIG. 10A, after alignment 1006, process 1000 can proceed to 1008. There, the aligned compressed wood pieces are bonded together, for example by glue / epoxy or hydrogen bonding. In an embodiment where hydrogen bonding is used, the bond 1008 is formed by compressing the pieces of wood. A press that presses aligned pieces together under high pressure, similar to the presses used to make Once bonded to form a laminate structure, process 1000 may continue at 1010. 100, where lamination can proceed as described above with respect to 114 of process 100. and / or (e.g., as described above with respect to 116 of process 100). (as described above).
[0081] FIG. 10A illustrates forming compressed wood pieces prior to joining, but embodiments of the disclosed subject matter are not limited thereto. Rather, in other embodiments, the joining of the pieces of wood is performed using a press to compress the pieces of wood. FIG. 10B illustrates such a process 1050. Similar to process 100 of 1, process 1050 requires the removal of sufficient lignin 106. The cutting 102 and chemical treatment 104 for the timber is then performed, followed by pressing 110 of the treated timber. These initial processes can be repeated at 1052 to form a chemically treated multi-layer structure. Generates individual pieces of wood.
[0082] Once a sufficient number of chemically treated wood pieces are prepared, the process 1050 proceeds to 1054. where chemically treated wood pieces are placed in preparation for joining. Each treated piece of wood can have a different orientation, which is the direction in which the lumen extends. 10A and 11A to 11F. As mentioned above, the wood pieces are arranged so that at least some of the pieces have different orientations relative to one another. The method may include placing the chemically treated wood pieces in a container such as a food processing container.
[0083] After alignment 1054, the process 1050 can proceed to 1056, where the aligned and The chemically treated pieces of wood are pressed together. Press 1056 compresses each piece of wood (i.e. It is effective in forming hydrogen bonds between opposing surfaces of the wood pieces (i.e., producing compressed wood pieces). Thus, the press 1056 simultaneously creates compression and bonding of the wood pieces to form a laminated structure. By repeating the cutting, chemical treatment, alignment, and pressing at 1058, further Alternatively, the process 1050 may continue to 1060. Proceed and adapt the laminate for use and / or use as in process 1000. It is possible.
[0084] Rinsing, pre-press correction, and post-press correction are shown separately in FIGS. 10A-10B. Although not shown, these embodiments may include rinsing, pre-preparation, and other steps similar to process 100 of FIG. It will be appreciated that the above may also include pre-press and / or post-press modifications.
[0085] In some embodiments, the laminate structure is made of multiple wood chips having different fiber orientations. For example, FIG. 12A shows a compressed wood stack made from individual wood chips 1202. 12 shows an embodiment of an exemplary manufacturing process for forming a laminate. Individual wood chips 1202 are 1204, each of which corresponds to a lumen extension direction and / or fiber alignment direction. Similar to the process 100 described above, wood chips 1202 may be composted by removing lignin therefrom. It is then subjected to chemical treatment to partially remove the The chemically modified wood chip assembly may be, for example, oriented as shown in FIG. 1B, orthogonal as shown in FIG. 1B, intersecting as shown in FIG. 11D-FIG. 11E, or For alignment, the orientation 1204 of the chip 1202 can be taken into consideration. , the orientation 1204 may be random within the multi-layer array. The adjacent wood chips can be pressed together to form a multi-layer laminate 1212 of compressed wood chips. The compressed wood chips may be held together by hydrogen bonds that form during the press 1210 .
[0086] In some embodiments, the laminate structure may comprise wood sheets and composites having different fiber orientations. For example, FIG. 12B shows a lumber slab made of individual wood chips 1202. 12, a pair of wood sheets 1220, 1224 are used to form a laminate of compressed wood. The manufacturing process is shown. The individual wood chips 1202 are aligned in the direction of the lumen extension and / or may have respective orientations 1204 corresponding to the fiber alignment direction. 220, 1224 correspond to the extension direction of the lumen and / or the alignment direction of the fibers therein. , may have respective orientations 1222, 1226.
[0087] Similar to process 100 above, wood sheets 1220, 1224 and wood chips 12 02 is chemically treated to partially remove lignin, and then the wood chips 1202 are The laminated structure can be assembled into a multi-layer structure by placing the laminated structure between the laminated structures 1220 and 1224 and via the laminated structure 1228. The assembly can be performed by taking into account the orientation of the sheets 1220, 1224 and the chip 1202. For example, at least the orientation 1204 of the chip 1202 can be 11B, orthogonal to each other as in FIG. 11B, or crossing or aligned as in FIG. 11D to FIG. 11E. Alternatively, at least the orientation 1204 of the chip 1202 may be In another embodiment, at least the sheet orientation 122 may be random within the multi-layer arrangement. 2, 1226 are perpendicular as shown in Figs. 11A-11B, and cross as shown in Figs. 11D-11E. In such an example, the wood may be arranged 1228 to be aligned or in alignment. The orientation 1204 of the chip 1202 is determined by the orientation of at least one of the sheets 1220, 1224. The alignment can be done according to the orientation or independent of the sheet orientation. For example, 1220, 1224 may be orthogonal to each other, but the orientation 1204 of the tip 1202 is substantially It may be random.
[0088] The multi-layer structure 1230 is then pressed at 1232 to form a multi-layer laminate of compressed wood 1234. Adjacent pieces of compressed wood can be formed between the presses 1232. The three layers of wood chips 1202 are held together by hydrogen bonds. 1220 and 1224, for example, a single layer or three layers of wood chips. It is also possible to provide fewer or additional layers of wood chips, such as more layers. In accordance with an embodiment of the disclosed subject matter, the features of the sheet and chip shown in FIGS. 12A-12B are For example, the stack 1234 may include a unit 1234 having a certain number and arrangement. A compressed sheet 1224 is disposed above and bonded to the compressed sheet 1220 of an adjacent unit 1234. In another example, the multi-layer laminate structure may include layer units of a wood chip. Repeating layers of sheet 1220 (or sheet 1224) with intervening layers of top 1202. The method may include steps.
[0089] The process of Figures 12A-12B can be used to produce anisotropic films with random or aligned orientations. A continuous wooden structure with little 34) Therefore, it is necessary to combine small wood chips that differ in size and orientation. These laminates can be combined to produce denser wood products. In fact, such laminated structures , easily expandable for use in a variety of applications and / or in a variety of sizes.
[0090] The rinse, pre-press correction, and post-press correction are shown separately in Figures 12A-12B. Although not shown, these embodiments may include rinsing, pre-pressing, and other steps similar to process 100 of FIG. It will be appreciated that the above may also include pre-press and / or post-press modifications. A specific number of compressed wood chips or sheets for a laminated structure are shown in Figures 12A-12B. However, other numbers of compressed wood chips or sheets may be used in accordance with one or more contemplated embodiments. Additionally, although a rectangular shape is shown in FIGS. 12A-12B, one or more Other shapes are possible in accordance with the above contemplated embodiments. In fact, the wood chips may be formed in a laminated structure. They may have irregular or different shapes / sizes before being joined to the structure. In accordance with the above contemplated embodiments, the orientation and alignment shown in FIGS. Other orientations and alignments that can be used are possible. In some embodiments, for example, to enhance anisotropy, In order to achieve this, the orientation of adjacent pieces (wood chips 1202 or sheets 1220, 1224) ) can be aligned.
[0091] In one or more of the first embodiments, the structure is chemically treated to partially remove lignin. On the other hand, the structure of the cellulosic lumen is substantially preserved, and further, the lumen is at least partially a first piece of natural plant material that is pressed in a first direction perpendicular to the extension of the lumen to collapse the first piece of natural plant material; Includes.
[0092] In the first embodiment or any other embodiment, the natural plant material is natural wood.
[0093] In the first embodiment or any other embodiment, the first piece is made of a material having a thickness comparable to that of natural wood. The first embodiment also has a thickness in the first direction that is reduced by at least 10% compared to the first embodiment. In any other embodiment, the first piece is at least 30% thicker than the thickness of the natural wood. % reduced thickness in said first direction. The first piece is a first piece having a thickness that is reduced by at least 60% compared to the thickness of natural wood. In the first embodiment or any other embodiment, the first piece has a thickness in the direction , having a thickness in said first direction that is reduced by at least 70% compared to the thickness of natural wood. In the first embodiment or any other embodiment, the first piece is made of a material having a thickness comparable to that of natural wood. The thickness in the first direction is reduced by at least 80% compared to the thickness in the first direction.
[0094] In the first embodiment or any other embodiment, the first piece comprises at least some In the first embodiment or any other embodiment, the natural plant material retains lignin. Between 1% and 99% of the lignin has been removed by chemical treatment. In an embodiment, between 5% and 95% of the lignin in the native plant material has been removed by chemical treatment.
[0095] In the first embodiment or any other embodiment, 23% to 30% of the lignin in the natural plant material 60% was removed by chemical treatment. One piece retains approximately 55% of the lignin from the native plant material after chemical treatment.
[0096] In the first embodiment or any other embodiment, facing the collapsed lumen in the first piece The moieties are held together by hydrogen bonds.
[0097] In the first embodiment or any other embodiment, the first piece is a natural plant prior to chemical treatment. Compared to other materials, the tensile strength, flexural strength, ductility, fracture toughness, scratch hardness, hardness coefficient, impact strength, The impact toughness, compressive strength and / or elastic stiffness are increased.
[0098] In the first embodiment or any other embodiment, the tensile strength of the first piece is increased by chemical treatment. The tensile strength of the natural plant material is at least two times greater than that of the natural plant material of the first embodiment or any of the first and second embodiments. In other embodiments, the tensile strength of the first piece is greater than the tensile strength of the native plant material prior to chemical treatment. In the first embodiment or any other embodiment, the first piece is at least 5 times larger than the first piece. The tensile strength is at least 350 MPa.
[0099] In the first embodiment or any other embodiment, the ductility of the first piece is determined by the following: The ductility of the natural plant material is equal to or at least 10 times greater than that of the first embodiment or any other embodiment. In this embodiment, the ductility of the first piece is less than the ductility of the native plant material prior to chemical treatment. At least 50 times larger.
[0100] In the first embodiment or any other embodiment, the fracture toughness of the first piece is determined by chemical treatment. The fracture toughness of the natural plant material is at least two times greater than that of the natural plant material of the first embodiment. In other embodiments, the fracture toughness of the first piece is greater than the fracture toughness of the natural plant material prior to chemical treatment. It is at least five times larger than the
[0101] In the first embodiment or any other embodiment, the elastic stiffness of the first piece is determined by chemical treatment. The elastic stiffness of the natural plant material is at least 5 times greater than that of the natural plant material of the first embodiment or any In other embodiments, the elastic stiffness of the first piece is greater than the elastic stiffness of the natural plant material prior to chemical treatment. It is at least 10 times larger than the
[0102] In the first embodiment or any other embodiment, the scratch hardness of the first piece is determined by chemical The scratch hardness of the natural plant material before treatment is at least 5 times greater. In any other embodiment, the scratch hardness of the first piece is less than that of the natural plant material prior to chemical treatment. At least 10 times greater than the scratch hardness.
[0103] In the first embodiment or any other embodiment, the impact toughness of the first piece is determined by chemical treatment. The impact toughness of the natural plant material is at least 2.5 times greater than that of the natural plant material of the first embodiment. In any other embodiment, the impact toughness of the first piece is equal to the impact toughness of the natural plant material prior to chemical treatment. at least five times larger than
[0104] In the first embodiment or any other embodiment, the hardness coefficient of the first piece is determined by chemical treatment. The hardness coefficient of the natural plant material is at least 5 times greater than that of the previous embodiment. In another embodiment, the hardness modulus of the first piece is greater than the hardness modulus of the natural plant material prior to chemical treatment. It is at least 10 times larger than the
[0105] In the first embodiment or any other embodiment, bending of the first piece along the extension direction The strength is at least 5 times greater in the tensile direction than the natural plant material before chemical treatment. The bending strength of the vertical first piece is at least as great as the bending strength of the natural plant material prior to chemical treatment. is also five times larger.
[0106] In the first embodiment or any other embodiment, bending of the first piece along the extension direction The strength is a first multiple greater than the bending strength of the natural plant material prior to chemical treatment and in the extension direction. The bending strength of the first piece perpendicular to the direction of the arrow is greater than the bending strength of the natural plant material before chemical treatment. A second multiple, the second multiple being greater than the first multiple. In another embodiment, the bending strength of the first piece along the extension direction is equal to that of the natural plant material prior to chemical treatment. A bending strength of the first piece perpendicular to the extension direction that is at least 5 times greater than the bending strength of the material. is at least 10 times greater than the bending strength of the natural plant material before chemical treatment.
[0107] In the first embodiment or any other embodiment, compression of the first piece along the extension direction The strength is at least 5 times greater than the compressive strength of the natural plant material before chemical treatment and in the extension direction. The compressive strength of the vertical first piece is at least as great as the compressive strength of the natural plant material before chemical treatment. is also five times larger.
[0108] In the first embodiment or any other embodiment, compression of the first piece along the extension direction The strength is a first multiple greater than the compressive strength of the natural plant material prior to chemical treatment and in the extension direction The compressive strength of the first piece perpendicular to the direction is greater than the compressive strength of the natural plant material before chemical treatment. A second multiple, the second multiple being greater than the first multiple. In the embodiment, the compressive strength of the first piece along the extension direction is The compressive strength of the first piece perpendicular to the direction of elongation is at least five times greater than the compressive strength of the material. , at least 30 times greater than the compressive strength of the natural plant material before chemical treatment.
[0109] In the first embodiment or any other embodiment, the first piece is a natural plant prior to chemical treatment. In the first embodiment or any other embodiment, the density is increased compared to the material. The density of the first piece is at least 1.5 times greater than the density of the natural plant material prior to chemical treatment. In the first embodiment or any other embodiment, the density of the first piece is At least two times greater than the density of natural plant materials.
[0110] In the first embodiment or any other embodiment, the first piece is a tensile strength material having a strength of 300 MPa cm 3 In the first or any other embodiment, the tensile strength is greater than 1 / g. The first piece is approximately 450MPa cm 3 / g.
[0111] In the first embodiment or any other embodiment, the collapsed luminal cellulose nanofibers The bars are substantially aligned along the extension direction.
[0112] In the first embodiment or any other embodiment, the first piece has, in cross section, There are virtually no gaps between the walls of the cavity.
[0113] In the first embodiment or any other embodiment, the natural plant material includes bamboo or natural wood. In the first embodiment or any other embodiment, the natural wood includes hardwood or softwood. In the first embodiment or any other embodiment, the natural wood is basswood, oak, polypropylene, or the like. Plastic, Ash, Alder, Aspen, Balsa, Beech, Birch, Cherry, Butter Nut, Chestnut, Cocobolo, Elm, Hickory, Maple, Oak, Padauk, Plum, Wood Lunat, willow, yellow poplar, bald cypress, cedar, cypress, Douglas fir, fir, bay Of the hemlock, larch, pine, sequoia, spruce, tamarack, juniper, and yew. Includes at least one of the following.
[0114] In the first embodiment or any other embodiment, the structure further comprises a cellulosic lumen. The extension of the lumen is at least partially collapsed while substantially preserving the structure of the lumen. Further pressing in the cross direction and partial removal of lignin by chemical treatment The first piece and the second piece are joined together along opposing faces. The extension direction of the lumen of the first piece is, for example, in a plan view, It intersects with the extension direction.
[0115] In the first embodiment or any other embodiment, the extension direction of the lumen of the first piece is The lumen of the two pieces is perpendicular to its extension.
[0116] In the first embodiment or any other embodiment, the first piece and the second piece are The first embodiment or any other embodiment is bonded to each other by hydrogen bonds between their opposing faces. In this embodiment, the first piece and the second piece are bonded to each other by an adhesive or are bonded together by epoxy.
[0117] In the first embodiment or any other embodiment, the first piece and the second piece are Flat sheets, blocks, sticks, strips, hollow shapes, films, thickness 20 mm It is formed as a thin film, wood chip, or wood flake less than 0 μm thick.
[0118] In the first embodiment or any other embodiment, the structure is for forming a multi-layer laminate structure. a plurality of additional first pieces coupled together with the first piece and the second piece; It further includes a second piece.
[0119] In the first embodiment or any other embodiment, the first piece includes a collapsed lumen and and / or non-natural particles incorporated within the outer surface of the first piece. In any other embodiment, the non-natural particles comprise hydrophobic nanoparticles. In other embodiments, the nanoparticles comprise SiO nanoparticles. In another embodiment, the non-natural particles render the first piece hydrophobic. In any other embodiment, the first piece has a static contact angle of at least 90°, or In the first embodiment or any other embodiment, the first The pieces have a static contact angle of greater than 150° and a dynamic contact angle of less than 5°.
[0120] In the first embodiment or any other embodiment, the first piece is made hydrophobic. In the first embodiment or any other embodiment, the hydrophobic chemical treatment is , epoxy resin, silicone oil, polyurethane, paraffin emulsion, acetic anhydride , Octadecyltrichlorosilane (OTS), 1H,1H,2H,2H-perfluorode Siltriethoxysilane, Fluoroecin, Polydimethylsiloxane (PDMS), Meta Acryloxymethyltrimethylsilane (MSi), a polyhedral oligomeric silsesquioxane (POSS), potassium methylsiliconate (PMS), dodecyl(trimethoxy)silane (DTMS), hexamethyldisiloxane, dimethyldiethoxysilane, tetraethoxy Silane, methyltrichlorosilane, ethyltrimethoxysilane, methyltriethoxysilane Silane, trimethylchlorosilane, phenyltrimethoxysilane, phenyltriethoxysilane Lanthanide, propyltrimethoxysilane, polymethylmethacrylate, polydiallyldimethyl Ammonium chloride (polyDADMAC), 3-(trimethoxysilyl)propyl Methacrylate (MPS, hydrophobic stearic acid, amphiphilic fluorinated triblock azidocopolymer Polymers, polyvinylidene fluoride and fluorinated silanes, n-dodecyltrimethoxysilane and sodium lauryl sulfate.
[0121] In the first embodiment or any other embodiment, the first piece is weather or salt water resistant. In the first embodiment or any other embodiment, the Chemical treatments for weathering or salt water include CDDC, Ammonium Copper Quaternary (ACQ), Chromium Copper arsenate (CCA), ammoniacal copper zinc arsenate (ACZA), copper naphthenate, acid chromium Acid copper, copper citrate, copper azole, 8-hydroxyquinoline copper, pentachlorophenol, Zinc naphthenate, copper naphthenate, creosote, titanium dioxide, propiconazole, tebu Conazole, cyproconazole, boric acid, borax, organic iodides (IPBC), and N a2B8O 13 Contains at least one of the following: 4H2O
[0122] In the first embodiment or any other embodiment, the structure comprises one or more of the first pieces. In the first embodiment or any other embodiment, the coating may further include a coating on the outer surface. Coatings can be oil-based paints, hydrophobic paints, polymer coatings, or fire-resistant coatings. In the first embodiment or any other embodiment, the refractory coating comprises a nitride coating. Boron, Montmorillonite clay, Hydrotalcite, Silicon dioxide (SiO2), Silica Sodium carbonate, calcium carbonate (CaCO3), aluminum hydroxide (Al(OH)3) , Magnesium hydroxide, (Mg(OH)2), Magnesium carbonate (MgCO3), Aluminium sulfate Aluminum, iron sulfate, zinc borate, boric acid, borax, triphenyl phosphate (TPP), Lamin, polyurethane, ammonium polyphosphate, phosphoric acid, phosphate ester, ammonium phosphate ammonium sulfate, phosphonic acid, diammonium phosphate (DAP), diammonium phosphate Ammonium hydrogen, monoammonium phosphate (MAP), guanylurea phosphate (GUP), guanidine dihydrogen phosphate, and antimony pentoxide.
[0123] In the first embodiment or any other embodiment, the first piece may have therein (e.g., The polymer is contained within a lumen that is completely or partially collapsed.
[0124] In the first embodiment or any other embodiment, the lumen in the first piece is completely collapsed. is.
[0125] In one or more second embodiments, the method includes: The natural plant material pieces are cut to substantially maintain the structure of the lumen while partially removing the lignin. treating the cavity with a chemical solution, such that after treatment, the cavity at least partially collapses; The chemically treated pieces of plant material are plated in a second direction transverse to the first direction for a first period of time. and scanning the
[0126] In the second embodiment or any other embodiment, the natural plant material is natural wood.
[0127] In the second embodiment or any other embodiment, the press is performed at a temperature of 20° C. to 120° C. The second embodiment or any other embodiment is carried out at a pressure of 0.5 MPa to 10 MPa. In the embodiment, pressing is carried out at a temperature of about 100° C. and a pressure of about 5 MPa.
[0128] In the second embodiment or any other embodiment, the first period of time is at least 5 minutes. In the second embodiment or any other embodiment, the first period of time is at least 1 hour. In the second or any other embodiment, the first period of time is at least 12 hours. In the second embodiment or any other embodiment, the first period of time is at least 24 hours. do.
[0129] In the second embodiment or any other embodiment, the compression is performed by extracting from chemically treated plant material. At the very least it is effective in removing water.
[0130] In the second or any other embodiment, the pressing is performed without an intermediate drying step. Executed after processing.
[0131] In the second embodiment or any other embodiment, the chemical solution is NaOH, Na2S, N aHSO3, SO2, H2O, Na2SO3, anthraquinone (AQ), Na2S n (n is an integer), CH3OH, C2H5OH, C4H9OH, HCOOH, NH3, p-TsO H, NH3-H2O, H2O2, NaClO, NaClO2, CH3COOH (acetic acid), The second embodiment or any other embodiment includes at least one of ClO2, ClO2, and Cl2. In one embodiment, the chemical solution comprises a mixture of NaOH and Na2SO3. Or in any other embodiment, the chemical solution is 2.5 M NaOH and 0.4 M Na In the second embodiment or any other embodiment, the chemical solution is boiling. do.
[0132] In the second embodiment or any other embodiment, the method further comprises the steps of: The chemically treated plant material pieces are then immersed in a solvent to remove any residual chemical solution in the pieces. In the second embodiment or any other embodiment, the solvent is boiled deionized. (DI) Contains water.
[0133] In the second embodiment or any other embodiment, the step of treating comprises treating natural plant material pieces. The second embodiment or any of the preceding embodiments further comprises the step of immersing the substrate in the chemical solution for at least 30 minutes. In another embodiment, the treatment comprises soaking the pieces of natural plant material in a chemical solution for at least one hour. In the second embodiment or any other embodiment, the natural plant material pieces are treated with a chemical solution. In the second embodiment or any other embodiment, the substrate is immersed in the solution for 0.1 to 72 hours. The treatment is carried out under vacuum so that the chemical solution penetrates the lumen of the natural plant material pieces.
[0134] In the second embodiment or any other embodiment, the low amount of hemicellulose and lignin At least a portion of the sintered body is retained by the piece after processing. In an embodiment, between 1% and 99% of the lignin is removed from the pieces by processing. In the second embodiment or any other embodiment, the treatment removes 5% to 95% of the lignin from the prepolymer. It has been removed from the piece.
[0135] In the second embodiment or any other embodiment, after pressing, the chemically treated pieces of plant material are The inner lumen collapses completely.
[0136] In the second embodiment or any other embodiment, the method further comprises the step of: prior to pressing, dissolving the polymer in a lumen; and after pressing, the polymer is within (e.g., partially or completely) the plant material. or completely collapsed lumen).
[0137] In the second embodiment or any other embodiment, the method further comprises the steps of: after pressing, The second embodiment or any other embodiment further includes coating one or more of the exterior surfaces. In an embodiment, the coating is an oil-based paint, a hydrophobic paint, a polymeric coating, or In the second embodiment or any other embodiment, the fire resistant coating is The coating is made of boron nitride, montmorillonite clay, hydrotalcite, silicon dioxide ( SiO2), sodium silicate, calcium carbonate (CaCO3), aluminum hydroxide ( Al(OH)3), magnesium hydroxide, (Mg(OH)2), magnesium carbonate (Mg CO3), aluminum sulfate, iron sulfate, zinc borate, boric acid, borax, triphenyl phosphate (TPP), melamine, polyurethane, ammonium polyphosphate, phosphoric acid, phosphate ester phosphate, ammonium sulfate, phosphonic acid, diammonium phosphate (D AP), ammonium dihydrogen phosphate, monoammonium phosphate (MAP), guanyl phosphate At least one of urea (GUP), guanidine dihydrogen phosphate, and antimony pentoxide Includes 1.
[0138] In the second embodiment or any other embodiment, the method further comprises the steps of: The method further includes depositing non-natural particles on an inner surface of the lumen, the non-natural particles disintegrating after pressing. In the second embodiment or any other embodiment, the non-natural particle is In the second embodiment or any other embodiment, the nanoparticles include Si Contains O2 nanoparticles.
[0139] In the second embodiment or any other embodiment, the non-natural particles are chemically treated plants. In the second embodiment or any other embodiment, after pressing, the chemical Chemically treated plant material pieces should have a static contact angle of at least 90° or a dynamic contact angle of less than 10°. In the second embodiment or any other embodiment, the pressed material is chemically treated. The wood pieces have a static contact angle of greater than 150° and a dynamic contact angle of less than 5°.
[0140] In the second embodiment or any other embodiment, the method further comprises: The method further includes subjecting the chemically treated plant material to a further chemical treatment to obtain a plant material that is In this or other embodiments, the treatment to render the surface hydrophobic may occur prior to (b). In the second embodiment or any other embodiment, the hydrophobic chemical treatment can be an epoxy. Silicone resin, silicone oil, polyurethane, paraffin emulsion, acetic anhydride, octadecane Decyltrichlorosilane (OTS), 1H,1H,2H,2H-perfluorodecyltrichlorosilane Ethoxysilane, Fluoroecin, Polydimethylsiloxane (PDMS), Methacrylo dimethyltrimethylsilane (MSi), polyhedral oligomeric silsesquioxane (POS S), potassium methylsiliconate (PMS), dodecyl(trimethoxy)silane (DT MS), hexamethyldisiloxane, dimethyldiethoxysilane, tetraethoxysilane , methyltrichlorosilane, ethyltrimethoxysilane, methyltriethoxysilane, Trimethylchlorosilane, Phenyltrimethoxysilane, Phenyltriethoxysilane, Propyltrimethoxysilane, Polymethylmethacrylate, Polydiallyldimethylammonium Poly(DADMAC), 3-(trimethoxysilyl)propyl methacrylate Rate (MPS, hydrophobic stearic acid, amphiphilic fluorinated triblock azide copolymer , polyvinylidene fluoride and fluorinated silane, n-dodecyltrimethoxysilane, and Sodium lauryl sulfate.
[0141] In the second or any other embodiment, the method partially removes lignin. After treatment, chemically treated wood may be further chemically treated to improve weather resistance or resistance to salt water. In the second or any other embodiment, the method further includes improving the weatherability or Chemical treatments for the saltwater include CDDC, Ammoniacal Copper Quaternary (ACQ), Chromated Arsenic Acid Copper (CCA), ammoniacal copper zinc arsenate (ACZA), copper naphthenate, acid copper chromate, Copper citrate, copper azole, 8-hydroxyquinoline copper, pentachlorophenol, naphthenic acid Zinc phosphate, copper naphthenate, creosote, titanium dioxide, propiconazole, tebuconazole borax, cyproconazole, boric acid, borax, organic iodide (IPBC), and Na2B 8O 13 Contains at least one of the following: 4H2O.
[0142] In the second or any other embodiment, the collapsed luminal cellulose nanofibers The bars are substantially aligned along a first direction. In an embodiment, after pressing, in cross section, the pieces include substantially no gaps between the walls of the lumen. stomach.
[0143] In the second embodiment or any other embodiment, the natural plant material includes bamboo or natural wood. In the second embodiment or any other embodiment, the natural wood includes hardwood or softwood. In the second embodiment or any other embodiment, the natural wood is selected from the group consisting of basswood, oak, and polypropylene. Plastic, Ash, Alder, Aspen, Balsa, Beech, Birch, Cherry, Butter Nut, Chestnut, Cocobolo, Elm, Hickory, Maple, Oak, Padauk, Plum, Wood Lunat, willow, yellow poplar, bald cypress, cedar, cypress, Douglas fir, fir, bay Of the hemlock, larch, pine, sequoia, spruce, tamarack, juniper, and yew. Includes at least one of the following.
[0144] In the second embodiment or any other embodiment, the pressed wood is treated with a 100% cellulose acetate solution, which is a 100% cellulose acetate solution. Then, the tensile strength, bending strength, ductility, fracture toughness, scratch hardness, hardness coefficient, impact At least one of toughness, compressive strength, and elastic stiffness is increased.
[0145] In the second or any other embodiment, after pressing, the pieces are A density at least twice as high as that of natural wood and a thickness that is comparable to that of the natural plant material before treatment. and a thickness in the second direction that is reduced by at least 60%. In another embodiment, the thickness of the piece after pressing is at least 100% compared to the thickness of natural wood. will also decrease by 70%.
[0146] In the second or any other embodiment, the press is between opposing portions of the collapsed lumen. forming hydrogen bonds to the
[0147] In the second or any other embodiment, the piece may be a flat sheet, a block, wood, sticks, strips, films, thin films, hollow shapes, wood chips, or wood flakes In the second embodiment or any other embodiment, the thin film is formed as a thin film having a thickness of 200 μm or more. It has a thickness below.
[0148] In the second embodiment or any other embodiment, the method further comprises repeating the treatment to remove lignin. and compressing one or more additional pieces of natural plant material into the resulting and b) bonding the compressed chemically treated pieces of plant material.
[0149] In the second or any other embodiment, a small amount of compressed and chemically treated plant material is At least some of the coupling pieces have first directions (e.g., in a plan view) that are mutually perpendicular to each other. In the second embodiment or any other embodiment, the first directions intersect with each other. Orthogonal.
[0150] In the second or any other embodiment, the bond is formed by hydrogen bonding between opposing surfaces. further pressing the pressed and chemically treated pieces of plant material together so as to include.
[0151] In the second embodiment or any other embodiment, each of the methods for partially removing lignin is After treatment, the chemically treated piece is placed in contact with another chemically treated piece. This is done simultaneously for the pieces arranged in such a way that
[0152] In the second or any other embodiment, the bonding is performed by bonding the chemically treated pieces of plant material together. This includes applying an adhesive or epoxy to the opposing surfaces.
[0153] In the second embodiment or any other embodiment, the method further comprises the step of: The method comprises machining a piece of plant material or forming a chemically treated piece of plant material into a desired shape or configuration. The method further includes the step of:
[0154] In one or more third embodiments, the structure has, in cross-section, gaps in the cell walls of the lumen. This includes compressed pieces of wood in which the lumen has completely collapsed, without any gaps.
[0155] In the third embodiment or any other embodiment, the compressed wood pieces are in a ratio of at least 5 to 2. In the third embodiment or any other embodiment, the compressed wood pieces are compressed in a ratio of about 5:1 It is compressed by a ratio of
[0156] In the third embodiment or any other embodiment, compressed wood pieces form the pieces. The third embodiment or any other embodiment contains less lignin than the natural wood used for In this embodiment, the compressed wood piece contains 1% to 99% of the lignin in natural wood. In this or any other embodiment, the compressed wood pieces contain 5% to 9% of the lignin in natural wood. In the third embodiment or any other embodiment, the compressed wood pieces include 1% to 25%. In the third embodiment or any other embodiment, the compressed wood pieces contain 5% lignin. Contains % to 16% lignin.
[0157] In the third embodiment or any other embodiment, compressed wood pieces form the pieces. Compared to natural wood used for Hardness, hardness, impact toughness, compressive strength and / or elastic stiffness are increased.
[0158] In the third embodiment or any other embodiment, the compressed wood piece has a compressible strength of at least 300 MP a cm 3 / g.
[0159] In one or more fourth embodiments, the laminate comprises a plurality of compressed wood pieces. Each piece has a cross-sectional area of The lumen of each piece is at least partially collapsed in the figure. At least some of the compressed wood pieces extend in directions that cross each other, forming a plurality of compressed wood pieces. The pieces of wood are bonded together.
[0160] In the fourth embodiment or any other embodiment, each piece has a gap between the walls of the lumen in cross section. It has a completely collapsed lumen with no gaps.
[0161] In the fourth embodiment or any other embodiment, adjacent pieces of compressed wood have opposing faces In the fourth embodiment or any other embodiment, adjacent pins are coupled to each other along the The surfaces are bonded to each other by hydrogen bonds between the opposing faces. In this embodiment, adjacent pieces are bonded together by adhesive or epoxy between opposing surfaces. are combined.
[0162] In the fourth embodiment or any other embodiment, the first set of compressed wood pieces is a first layer. a second set of compressed wood pieces is placed in a second layer on the first layer, and and the second layer are bonded to one another via opposing faces between adjacent pieces from each layer. can be.
[0163] In the fourth embodiment or any other embodiment, the extension direction of adjacent pairs of compressed wood pieces is (i.e., in plan view) intersect with each other. In this embodiment, the extension directions of adjacent pairs of compressed wood pieces are perpendicular to each other.
[0164] In the fourth embodiment or any other embodiment, each compressed wood piece has a ratio of at least 5 to 2. In the fourth embodiment or any other embodiment, each compressed piece of wood is compressed with about 5 pairs of wood. It is compressed at a ratio of 1.
[0165] In the fourth embodiment or any other embodiment, each compressed piece of wood is made of The fourth embodiment or any of the preceding embodiments contains less lignin than the natural wood used for producing the wood. In another embodiment, each compressed piece of wood contains between 1% and 99% of the lignin in natural wood. In this embodiment or any other embodiment, each compressed wood piece contains 5% of the lignin in natural wood. Includes %~95%.
[0166] In the fourth embodiment or any other embodiment, each compressed wood piece has between 1% and 25% ribs. In the fourth embodiment or any other embodiment, each compressed wood piece contains 5% to 1 Contains 6% lignin.
[0167] In the fourth embodiment or any other embodiment, a fluorine-containing polymer is used to form the pieces. Compared to natural wood, each compressed piece of wood has tensile strength, bending strength, ductility, fracture toughness, scratch resistance, and The hardness, hardness, impact toughness, compressive strength and / or elastic stiffness are increased.
[0168] In the fourth embodiment or any other embodiment, each compressed wood piece is a flat sheet, a block, Sticks, strips, hollow shapes, films, thin films less than 200μm thick, wood chips , or formed as wood flakes.
[0169] In the fourth embodiment or any other embodiment, each compressed wood piece is at least 300 mm long. Pa cm 3 / g.
[0170] In one or more of the fifth embodiments, the material may have the structure of the first or third embodiment, the structure of the fourth embodiment, or a structure formed by the method of the third embodiment.
[0171] In one or more sixth embodiments, the material of the fifth embodiment is used in automobiles, trains, trucks, On or within an airplane, boat, ship, or any other means of transportation, vehicle, or conveyance It is formed as an external component.
[0172] In one or more sixth embodiments, the material of the fifth embodiment is a container, box, or forms part of the shipping crate.
[0173] In one or more sixth embodiments, the material of the fifth embodiment is used in warehouses, factories, office buildings, As an interior or exterior component of a barn, home, or any other building or structure In one or more sixth embodiments, the material of the fifth embodiment is used in a display, Decorations, window frames, picture frames, doors or door frames, tables, desks, chairs, cabinets, wardrobes Forms a living room, a bed, or any other piece of furniture or home accent. In the sixth embodiment above, the material of the fifth embodiment is used for bridges, docks, decks, or plasterwork. In one or more sixth embodiments, the material of the fifth embodiment forms part of the In one or more sixth embodiments, the material of the fifth embodiment is Form part of a protective cover, blast shield, or other protective device. In the form, the material of the fifth embodiment forms part of a tool, exercise equipment, or sporting goods. do.
[0174] In this application, the use of the singular includes the plural, unless otherwise stated, and The separate use of "and" includes the other, i.e., "and / or." The terms "including" or "having" as well as "in "includes," "included," "has," or "has The use of other forms such as "had" has the same effect as "comprising." is intended to have a general scope and should not be construed as limiting.
[0175] Ranges described herein include the endpoints and all values between the endpoints. It will be understood that "substantially" and "approximately" are ximately," "essentially," "nearly " or similar language when used in conjunction with a specific value, unless otherwise stated. Up to 10% variation in the values is intended to be included.
[0176] The above discussion applies in some cases to laboratory-generated examples, but these examples are not intended to be construed as limiting the scope of the present invention. Therefore, when the quantities and techniques are applied to the laboratory example, they are limited. This document should not be construed as defining the scope of the present invention.
[0177] Thus, in accordance with the present disclosure, strong, durable structural timber and methods for making and using same are provided. It will be apparent that this disclosure will enable many alternatives, modifications, and variations. Although particular examples have been shown and described in detail to illustrate the application of the principles of the invention, the invention It is understood that other implementations may be used without departing from such principles. For example, , the disclosed features may be combined, rearranged, or omitted to create additional embodiments. Although it may be possible, certain disclosed features may be used to advantage without the corresponding use of other features. Accordingly, applicants reserve the right to make and use all such alternatives which fall within the spirit and scope of the present invention. , modifications, equivalents, and variations are intended to be covered herein.
Claims
1. The lignin was partially removed by chemical treatment while the cellulosic lumen structure was substantially preserved. and removing the lumen, and then removing the lumen in a direction perpendicular to the direction of extension of the lumen so that the lumen is at least partially collapsed. A structure comprising a first piece comprising natural wood pressed in a first direction.
2. The thickness of the first piece in the first direction is smaller than the thickness of the natural wood.
2. The structure of claim 1, wherein both are reduced by 60%.
3. The thickness of the first piece is reduced by at least 80% compared to the thickness of the natural wood. The structure of claim 2 .
4. 10. The method of claim 1, wherein the first piece retains at least some lignin. structure.
5. 5% to 95% of the lignin in natural wood has been removed by chemical treatment. The structure of the mount.
6. 23% to 60% of the lignin in natural wood has been removed by chemical treatment. The structure described.
7. The first piece retains about 55% of the natural wood lignin after the chemical treatment. The structure of claim 6.
8. Opposite portions of the collapsed lumen in the first piece are held together by hydrogen bonds. The structure of claim 1 .
9. The first piece has a tensile strength, a bending strength, an elongation strength, and a tensile strength, which are greater than those of the natural wood before chemical treatment. The properties of the material, such as fracture toughness, scratch hardness, hardness coefficient, impact toughness, compressive strength and / or elastic stiffness, The structure of claim 1 , wherein
10. The tensile strength of the first piece is at least as great as the tensile strength of the natural wood prior to chemical treatment.
10. The structure of claim 9, wherein the distance between the first and second electrodes is five times greater.
11. 10. The structure of claim 9, wherein the first piece has a tensile strength of at least 350 MPa. Construction.
12. 10. The method of claim 9, wherein the ductility of the first piece is the same as the ductility of natural wood prior to the chemical treatment. The structure described in
13. The fracture toughness of the first piece is at least as great as the fracture toughness of natural wood prior to the chemical treatment.
10. The structure of claim 9, wherein the distance between the first and second electrodes is five times greater.
14. The elastic stiffness of the first piece is at least as great as the elastic stiffness of natural wood before the chemical treatment.
10. The structure of claim 9, wherein the distance between the first and second electrodes is five times greater.
15. The scratch hardness of the first piece is greater than the scratch hardness of natural wood prior to the chemical treatment. The structure of claim 9, which is at least 5 times larger.
16. The impact toughness of the first piece is at least as great as the impact toughness of natural wood prior to the chemical treatment.
10. The structure of claim 9, wherein the distance between the first and second electrodes is five times greater.
17. The hardness coefficient of the first piece is less than the hardness coefficient of natural wood before the chemical treatment.
10. The structure of claim 9, wherein the distance between the first and second electrodes is five times greater.
18. The bending strength of the first piece along the extension direction is the bending strength of natural wood before the chemical treatment. The bending strength of the first piece perpendicular to the extension direction is at least 5 times greater than the bending strength of the first piece perpendicular to the extension direction.
10. The structure of claim 9, wherein the bending strength is at least 5 times greater than that of natural wood prior to chemical treatment.
19. The compressive strength of the first piece along the extension direction is the compressive strength of natural wood before the chemical treatment. The compressive strength of the first piece perpendicular to the extension direction is at least 5 times greater than the 10. The structure of claim 9, having a compressive strength at least 5 times greater than that of natural wood prior to chemical treatment.
20. The first piece has an increased density compared to the natural wood prior to chemical treatment. Item 2. The structure according to item 1.
21. The density of the first piece is at least two times greater than the density of the natural wood prior to the chemical treatment.
21. The structure of claim 20.
22. The first piece has a compressive strength of 300 MPa cm 3 / g or more. Item 2. The structure according to item 1.
23. The first piece has a compressible strength of about 450 MPa cm 3 23. The method of claim 22, wherein the tensile strength of the tensile strength is 1.0 / g. The structure described in
24. The cellulose nanofibers in the collapsed lumen are substantially aligned along the extension direction.
2. The structure of claim 1 .
25. In a cross-sectional view, the first piece includes substantially no gaps between the walls of the lumen. Item 2. The structure according to item 1.
26. The structure of claim 1 , wherein the natural wood comprises hardwood or softwood.
27. The natural wood includes basswood, oak, poplar, ash, alder, aspen, and buckthorn. Rusa wood, beech, birch, cherry, butternut, chestnut, cocobolo, elm, hickory, Maple, Oak, Padauk, Plum, Walnut, Willow, Yellow Poplar, Ragwood Japanese cedar, cypress, Douglas fir, fir, hemlock, larch, pine, sequoia, spruce, ta 27. The method of claim 26, comprising at least one of the following: marac, juniper, and yew. Structure of.
28. The lignin is partially removed by chemical treatment while the cellulosic lumen structure is substantially preserved. and removing the lumen, and then removing the lumen in a direction perpendicular to the direction of extension of the lumen so that the lumen is at least partially collapsed. a second piece including natural wood pressed in an interleaving direction; The first piece and the second piece are joined to each other along opposing surfaces, The extension direction of the lumen of the first piece intersects with the extension direction of the lumen of the second piece. The structure according to claim 1.
29. The extending direction of the inner cavity of the first piece is perpendicular to the extending direction of the inner cavity of the second piece.
30. The structure of claim 28 .
30. The first piece and the second piece are bonded to each other by hydrogen bonds between their facing surfaces.
30. The structure of claim 28 which is bonded to one another.
31. The first piece and the second piece are secured to each other by adhesive or epoxy between their facing surfaces.
30. The structure of claim 28, wherein the heteroaryl groups are bonded to each other by an alkyl group.
32. Each of the first piece and the second piece may be a flat sheet, a block, Sticks, strips, hollow shapes, films, thin films less than 200 μm thick, wood chips, 30. The structure of claim 28, wherein:
33. a plurality of additional first pieces coupled together with the first piece and the second piece; 30. The structure of claim 28, further comprising a first piece and a second piece to form a multi-layer laminate structure. 。
34. The first piece may be a flat sheet, a block, a stick, a strip, a hollow shape. , a film, a thin film less than 200 μm thick, wood chips, or wood flakes. The structure of claim 1 .
35. The first piece is assembled within the collapsed lumen and / or the outer surface of the first piece.
10. The structure of claim 1 comprising embedded non-natural particles.
36. 36. The structure of claim 35, wherein the non-natural particles comprise hydrophobic nanoparticles.
37. The nanoparticles are SiO 2 37. The structure of claim 36 comprising nanoparticles.
38. 36. The structure of claim 35, wherein the non-natural particles render the first piece hydrophobic.
39. The first piece has a static contact angle of at least 90° or a dynamic contact angle of less than 10°.
40. The structure of claim 38, having the following structure:
40. The first piece has a static contact angle of greater than 150° and a dynamic contact angle of less than 5°.
40. The structure of claim 39.
41. 10. The structure of claim 1, wherein the first piece is chemically treated to render it hydrophobic. 。
42. Hydrophobic chemical treatments include epoxy resins, silicone oils, polyurethanes, paraffin emma elution, acetic anhydride, octadecyltrichlorosilane (OTS), 1H,1H,2H,2 H-perfluorodecyltriethoxysilane, Fluoroecin, Polydimethylsiloxane (PDMS), methacryloxymethyltrimethylsilane (MSi), polyhedral oligomer Silsesquioxane (POSS), potassium methylsiliconate (PMS), dodecyl ( Trimethoxysilane (DTMS), Hexamethyldisiloxane, Dimethyldiethoxysilane Silane, tetraethoxysilane, methyltrichlorosilane, ethyltrimethoxysilane, Trimethyltriethoxysilane, trimethylchlorosilane, phenyltrimethoxysilane, phenyl Nyltriethoxysilane, propyltrimethoxysilane, polymethylmethacrylate, poly Poly(diallyldimethylammonium chloride) (polyDADMAC), 3-(trimethoxy (Silyl)propyl methacrylate (MPS), hydrophobic stearic acid, amphiphilic fluorinated Triblock azide copolymer, polyvinylidene fluoride and fluorinated silane, n-dodecyl silane, dimethyltrimethoxysilane, and sodium lauryl sulfate, 42. The structure of claim 41.
43. The first piece is chemically treated to be resistant to weather or salt water. Item 2. The structure according to item 1.
44. The chemical treatment for weathering or salt water resistance is CDDC, ammoniacal copper nitrate, Class 4 (ACQ), chromated copper arsenate (CCA), ammoniacal copper zinc arsenate (ACZA), Copper phthalate, acid copper chromate, copper citrate, copper azole, 8-hydroxyquinoline copper, Pentachlorophenol, zinc naphthenate, copper naphthenate, creosote, titanium dioxide, Propiconazole, tebuconazole, cyproconazole, boric acid, borax, organic iodides (IPBC), and Na 2 B 8 O 13 ・4H 2 Claims including at least one of O.
44. The structure according to claim 43.
45. 10. The structure of claim 1, further comprising a coating on one or more exterior surfaces of the first piece. Construction.
46. The coating may be an oil-based paint, a hydrophobic paint, a polymer coating, or a fire-resistant coating.
46. The structure of claim 45, comprising a coating.
47. The fire resistant coating may be composed of boron nitride, montmorillonite clay, hydrotalcite, , silicon dioxide (SiO 2 ), sodium silicate, calcium carbonate (CaCO 3 ), hydroxy acid Aluminum chloride (Al(OH) 3 ), magnesium hydroxide, (Mg(OH) 2 ), Carbonate Magnesium (MgCO 3 ), aluminum sulfate, iron sulfate, zinc borate, boric acid, borax, Triphenyl phosphate (TPP), melamine, polyurethane, ammonium polyphosphate, Phosphonic acid, phosphate ester, ammonium phosphate, ammonium sulfate, phosphonic acid, diphosphate Ammonium (DAP), Ammonium Dihydrogen Phosphate, Ammonium Monophosphate (MAP) , guanylurea phosphate (GUP), guanidine dihydrogen phosphate, and antimony pentoxide.
47. The structure of claim 46, comprising at least one of:
48. The structure of claim 1 , wherein the first piece includes a polymer therein.
49. The structure of claim 1 , wherein the lumen within the first piece is completely collapsed.
50. (a) forming a cellulosic membrane having a first lumen extending in a first direction while substantially preserving the structure of the lumen; treating the natural wood pieces with a chemical solution to partially remove lignin; (b) after said treatment step, chemical treatment is performed so that said lumen at least partially collapses; The piece of wood is pressed in a second direction intersecting the first direction for a first period of time. Press step and A method comprising:
51. The pressing step is performed at a temperature of 20° C. to 120° C. and a pressure of 0.5 MPa to 10 MPa.
51. The method of claim 50, wherein the method is performed in
52. The pressing step is carried out at a temperature of about 100° C. and a pressure of about 5 MPa.
52. The method according to claim 51.
53. 51. The method of claim 50, wherein the first period of time is at least 5 minutes.
54. 54. The method of claim 53, wherein the first period of time is one hour.
55. The pressing step is effective to remove at least water from the chemically treated wood.
51. The method of claim 50, wherein:
56. The pressing step is carried out after the treatment without any intermediate drying step; 51. The method of claim 50.
57. The chemical solution is NaOH, Na 2 S, NaHSO 3 , S.O. 2 , H 2 O, Na 2 SO 3 , anthraquinone (AQ), Na 2 S n (n is an integer), CH 3 O.H., C. 2 H 5 O.H., C. 4 H 9 Yes, yes, yes. 3 、p-TsOH、NH 3 -H 2 O、H 2 O 2 alッ , NaClO 2 , C.H. 3 COOH (acetic acid), ClO 2 , and Cl 2 At least one of 51. The method of claim 50, comprising one.
58. The chemical solution is NaOH and Na 2 SO 3 58. The method of claim 57, comprising a mixture of 。
59. The chemical solution was 2.5 M NaOH and 0.4 M Na 2 SO 3 Claim 5 8. The method according to claim 8.
60. 51. The method of claim 50, wherein the chemical solution is boiling.
61. Before the pressing step and after the treating step, the chemically treated wood pieces are soaked in a solvent.
51. The method of claim 50, further comprising the step of: immersing the wood pieces in a The method described above.
62. 62. The method of claim 61, wherein the solvent comprises boiling deionized (DI) water.
63. The treating step comprises soaking the natural wood pieces in the chemical solution for at least 0.5 hours.
51. The method of claim 50, comprising the steps of:
64. The natural wood pieces are soaked in the chemical solution for 0.1 to 72 hours.
63. The method according to claim 63.
65. The treating step is performed under vacuum so that the chemical solution penetrates the internal cavities of the natural wood pieces.
51. The method of claim 50, wherein
66. After the treatment step, at least a portion of the hemicellulose and lignin is 51. The method of claim 50, wherein the piece is held by a strip.
67. the treatment step removes between 5% and 95% of the lignin from the wood pieces; 67. The method of claim 66.
68. After the pressing step, the internal cavities within the chemically treated wood pieces completely collapse.
51. The method according to claim 50.
69. The method further includes the step of introducing a polymer into the lumen prior to the pressing step, 51. The method of claim 50, wherein the polymer is disposed within the lumen after the disposition.
70. After the pressing step, coating one or more outer surfaces of the wood pieces.
51. The method of claim 50, further comprising:
71. The coating can be oil-based paint, hydrophobic paint, polymer coating, or fire-resistant coating.
71. The method of claim 70, comprising:
72. The fire resistant coating may be composed of boron nitride, montmorillonite clay, hydrotalcite, , silicon dioxide (SiO 2 ), sodium silicate, calcium carbonate (CaCO 3 ), hydroxy acid Aluminum chloride (Al(OH) 3 ), magnesium hydroxide, (Mg(OH) 2 ), Carbonate Magnesium (MgCO 3 ), aluminum sulfate, iron sulfate, zinc borate, boric acid, borax, Triphenyl phosphate (TPP), melamine, polyurethane, ammonium polyphosphate, Phosphonic acid, phosphate ester, ammonium phosphate, ammonium sulfate, phosphonic acid, diphosphate Ammonium (DAP), Ammonium Dihydrogen Phosphate, Ammonium Monophosphate (MAP) , guanylurea phosphate (GUP), guanidine dihydrogen phosphate, and antimony pentoxide.
72. The method of claim 71, comprising at least one of:
73. depositing a plurality of non-natural particles on an interior surface of the lumen prior to the pressing step. and wherein after said pressing, said non-natural particles are incorporated into said collapsed lumen.
50. The method according to claim 50.
74. 74. The method of claim 73, wherein the non-natural particles comprise hydrophobic nanoparticles.
75. The nanoparticles are SiO 2 75. The method of claim 74, comprising nanoparticles.
76. 74. The method of claim 73, wherein the non-natural particles render the chemically treated wood pieces hydrophobic. Law.
77. After the pressing step, the chemically treated wood pieces have a static contact angle of at least 90°.
77. The method of claim 76, wherein the surface has a dynamic contact angle of less than 10° or less than 10°.
78. After the pressing step, the chemically treated wood pieces have a static contact angle of greater than 150°. and a dynamic contact angle of less than 5°.
79. After (a), the chemically treated wood is subjected to a further chemical treatment to render the wood hydrophobic.
51. The method of claim 50, further comprising the step (c) of:
80. 80. The method of claim 79, wherein (c) occurs before (b).
81. Hydrophobic chemical treatments include epoxy resins, silicone oils, polyurethanes, paraffin emma elution, acetic anhydride, octadecyltrichlorosilane (OTS), 1H,1H,2H,2 H-perfluorodecyltriethoxysilane, Fluoroecin, Polydimethylsiloxane (PDMS), methacryloxymethyltrimethylsilane (MSi), polyhedral oligomer Silsesquioxane (POSS), potassium methylsiliconate (PMS), dodecyl ( Trimethoxysilane (DTMS), Hexamethyldisiloxane, Dimethyldiethoxysilane Silane, tetraethoxysilane, methyltrichlorosilane, ethyltrimethoxysilane, Trimethyltriethoxysilane, trimethylchlorosilane, phenyltrimethoxysilane, phenyl Nyltriethoxysilane, propyltrimethoxysilane, polymethylmethacrylate, poly Poly(diallyldimethylammonium chloride) (polyDADMAC), 3-(trimethoxy (Silyl)propyl methacrylate (MPS), hydrophobic stearic acid, amphiphilic fluorinated Triblock azide copolymer, polyvinylidene fluoride and fluorinated silane, n-dodecyl silane, dimethyltrimethoxysilane, and sodium lauryl sulfate, 80. The method of claim 79.
82. After (a), the chemically treated wood may be subjected to a further chemical treatment to prevent it from being exposed to weather or salt water.
51. The method of claim 50, further comprising the step (c) of increasing resistance to.
83. The chemical treatment to make the metal resistant to weather or salt water is CDDC, Ammoniacal Copper Quaternary ( ACQ), chromated copper arsenate (CCA), ammoniacal copper zinc arsenate (ACZA), naphthene Acid copper, acid copper chromate, copper citrate, copper azole, 8-hydroxyquinoline copper, pentacyl Rorophenol, zinc naphthenate, copper naphthenate, creosote, titanium dioxide, propyl Conazole, tebuconazole, cyproconazole, boric acid, borax, organic iodides (IP B C), and Na 2 B 8 O 13 ・4H 2 82. The method of claim 82, further comprising at least one of: The method described above.
84. The cellulose nanofibers in the collapsed lumen are substantially aligned along the first direction.
51. The method of claim 50, wherein
85. After the pressing step, the piece of wood is, in cross section, substantially spaced apart between the walls of the cavity.
51. The method of claim 50, wherein said method does not include
86. 51. The method of claim 50, wherein the natural wood comprises hardwood or softwood.
87. The natural wood includes basswood, oak, poplar, ash, alder, aspen, and buckthorn. Rusa wood, beech, birch, cherry, butternut, chestnut, cocobolo, elm, hickory, Maple, Oak, Padauk, Plum, Walnut, Willow, Yellow Poplar, Ragwood Japanese cedar, cypress, Douglas fir, fir, hemlock, larch, pine, sequoia, spruce, ta 87. The method according to claim 86, comprising at least one of the following: marac, juniper, and yew. Method of posting.
88. After the pressing step, the tensile strength, bending strength, ductility, fracture toughness, scratch resistance, etc. of the wood pieces are At least one of hardness, hardness modulus, impact toughness, compressive strength, and elastic stiffness is determined by the process.
51. The method of claim 50, wherein the thermal expansion coefficient is increased compared to that of natural wood prior to the treatment step.
89. After the pressing step, the piece of wood is a density at least twice the density of natural wood prior to said treatment step; The thickness of the natural wood is reduced by at least 60% compared to the thickness of the natural wood before the treatment step. The thickness in the direction of 2; 51. The method of claim 50, having the following structure:
90. The thickness of the piece of wood after the pressing step is at least 100% greater than the thickness of the natural wood.
90. The method of claim 89, wherein the concentration of .alpha.-tocopherol is also reduced by 80%.
91. The pressing step forms hydrogen bonds between opposing portions of the collapsed lumen.
51. The method of claim 50, comprising:
92. The wood piece may be a flat sheet, a block, a stick, a strip, a film, a thin film, a hollow 51. The method of claim 50, wherein the wood is formed into shapes, wood chips, or wood flakes.
93. 93. The method of claim 92, wherein the thin film has a thickness of 200 μm or less.
94. (c) repeating (a) and (b) on one or more additional pieces of natural wood. 、 (d) bonding the resulting pressed and chemically treated wood pieces; 51. The method of claim 50, further comprising:
95. A first portion of each of the joined pressed and chemically treated wood pieces is The method of claim 94, wherein the directions of intersect with each other.
96. 96. The method of claim 95, wherein the intersecting first directions are perpendicular to each other.
97. (d) pressing and chemically treating the pressed wood so that opposing surfaces are hydrogen bonded; 95. The method of claim 94, further comprising the step of pressing the pieces.
98. After each (a), the chemically treated wood pieces are placed in contact with other chemically treated pieces. The method further includes the step of placing (b) pressing the pieces of wood so as to produce (d) a bond 95. The method of claim 94, performed simultaneously.
99. (d) applying adhesive or epoxy to the opposing surface of the chemically treated wood piece; 95. The method of claim 94, comprising:
100. (b) machining the chemically treated wood pieces; or 51. The method of claim 50, further comprising forming the cut wood pieces into a desired shape or configuration. How to.
101. In cross-section, the lumen is completely collapsed with no gaps between the lumen cell walls. The structure includes compressed wood pieces.
102. 102. The method of claim 101, wherein the compressed wood pieces are compressed at a ratio of at least 5 to 2. structure.
103. 103. The structure of claim 102, wherein the compressed wood pieces are compressed at a ratio of about 5 to 1.
104. The compressed wood pieces have less rigging than the natural wood used to form the wood pieces. The structure of claim 101, comprising nin.
105. The compressed wood piece contains 5% to 95% of the lignin in natural wood. The structure described.
106. 106. The structure of claim 105, wherein the compressed wood pieces contain between 1% and 25% lignin.
107. The compressed wood pieces have a tensile strength greater than that of the natural wood used to form the wood pieces. Strength, flexural strength, ductility, fracture toughness, scratch hardness, hardness coefficient, impact toughness, compressive strength and and / or increased elastic stiffness.
108. The compressed wood piece has a compressive strength of at least 300 MPa cm 3 / g of tensile strength.
102. The structure of claim 101.
109. A laminate comprising a plurality of compressed wood pieces, each piece being at least partially a collapsed lumen, the lumen extending in a respective extension direction; The extension directions of at least some of the compressed wood pieces intersect with each other, and A laminate, wherein the plurality of compressed wood pieces are bonded together.
110. Each piece has, in cross-section, a completely collapsed lumen with no gaps between the walls of the lumen.
110. The laminate of claim 109.
111. 12. The method of claim 11, wherein adjacent pieces of compressed wood are bonded to one another along opposing faces.
10. The laminate according to claim 0.
112. said adjacent pieces of wood being bonded to one another by hydrogen bonds between said opposing faces. Item 112. The laminate according to item 111.
113. The adjacent pieces of wood are bonded together between the opposing surfaces with an adhesive or epoxy. The laminate of claim 111.
114. the first set of compressed wood pieces is disposed in a first layer; a second set of compressed wood pieces is disposed in a second layer on the first layer; and The first layer and the second layer are connected to each other via opposing faces between adjacent pieces from each layer.
111. The laminate of claim 110, which is bonded.
115. 111. The method of claim 110, wherein adjacent pairs of compressed wood pieces extend in directions perpendicular to each other. Laminate.
116. 111. The method of claim 110, wherein each piece of compressed wood is compressed at a ratio of at least 5 to 2. Layered body.
117. 117. The laminate of claim 116, wherein each piece of compressed wood is compressed at a ratio of about 5 to 1.
118. Each piece of compressed wood contains less lignin than the natural wood used to form the piece. The laminate of claim 110, comprising:
119. According to claim 118, each piece of compressed wood contains 5% to 95% of the lignin in natural wood. A laminate of.
120. 120. The laminate of claim 119, wherein the compressed wood pieces contain 5% to 16% lignin.
121. Each piece of compressed wood has an increased Tensile strength, bending strength, ductility, fracture toughness, scratch hardness, hardness coefficient, impact toughness, compressive strength 111. The laminate of claim 110, having a degree of elasticity and / or elastic stiffness.
122. Each piece of compressed wood can be a flat sheet, block, stick, strip, hollow shape, The present invention is directed to a method for manufacturing a wood-based material comprising the steps of: forming a film, a thin film having a thickness of less than 200 μm, a wood chip, or a wood flake; The laminate of claim 110.
123. Each piece of compressed wood has a compressive strength of at least 300 MPa cm 3 / g of tensile strength. Item 111. The laminate according to item 110.
124. A structure according to any one of claims 1 to 49, A structure according to any one of claims 101 to 108, A laminate according to any one of claims 109 to 123, or A structure formed by the method of any one of claims 50 to 100; Including, materials.
125. The material may be transported by a car, train, truck, plane, boat, ship, or any other transport. As an internal or external component of a means, vehicle, or conveyance The material of claim 124.
126. 124. The material forming part of a container, box, or shipping crate. The material described in.
127. The material may be a warehouse, a factory, an office building, a barn, a house, or any other building or structure.
125. The method of claim 124, wherein the device is formed as an internal or external component of a structure. Materials as described.
128. The materials can be used for displays, decorations, window frames, picture frames, doors or door frames, tables, desks, Chair, cabinet, wardrobe, bed, or any other piece of furniture or home accent.
125. The material of claim 124 forming part of another object.
129. The material forms part of a bridge, dock, deck, or platform.
124. The material described in 124.
130. 125. The material of claim 124, wherein the material forms part of a musical instrument.
131. The material forms part of a protective cover, blast shield, or other protective device. The material of claim 124.
132. 125. The method of claim 124, wherein the material forms part of a tool, exercise equipment, or sporting goods. Materials as described.
Citation Information
Patent Citations
Production method of compressed compact carbonized wood
CN106493815A